Near-infrared absorbing glass and near-infrared cut filter

A near-infrared absorbing glass with a specific composition and O/P ratio is developed to maintain high visible transmittance and near-infrared cutting performance, even when thinner, and to improve weather resistance, addressing the challenges faced by existing near-infrared cut filters.

JP2025038189AActive Publication Date: 2025-03-18HOYA CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024224633
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-07-10
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2041-05-31

AI Technical Summary

Technical Problem

Near-infrared cut filters face challenges in maintaining high transmittance in the visible range while achieving excellent near-infrared cutting performance, especially when the thickness of the near-infrared absorbing glass is reduced, and in withstanding high temperature and high humidity environments.

Method used

The development of a near-infrared absorbing glass composition that includes four or more major cations such as P, Li, Cu, Al, Ba, Sr, Ca, Mg, Zn, K, Na, La, Gd, and Y, with P, Li, and Cu as essential cations, and a specific ratio of O ions to P ions to optimize the glass's properties.

Benefits of technology

This glass composition maintains high transmittance in the visible range, exhibits excellent near-infrared cutting ability, and enhances weather resistance, even when thinner, thus addressing the limitations of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038189000023
    Figure 2025038189000023
  • Figure 2025038189000001
    Figure 2025038189000001
  • Figure 2025038189000002
    Figure 2025038189000002
Patent Text Reader

Abstract

To provide a near-infrared absorbing glass that offers high visible light transmittance despite reduced thickness, exhibits excellent near-infrared blocking ability, and can suppress deterioration in weather resistance.SOLUTION: The present invention provides a glass comprising P ions, Li ions, and Cu ions as essential cations and comprising at least O ions as anions, wherein the ratio of the content of O ions to the content of P ions is 3.15 or less, the content of O ions is 90.0 anion% or more in the glass composition in terms of anion%, the total content of oxides of major cations is 90.0% or more, the total content of MgO and Al2O3 is 8.0% or less, the ratio of the total content of Na2O, K2O, and ZnO to the content of Li2O is 2.4 or less, the total content of B2O3 and SiO2 is 3.0% or less, and the CuO content is α1% or more, where α1 is a value calculated by formula 1 (R is the ratio of O ions to P ions): (Formula 1) α1=70400×exp(-2.855×R).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a near-infrared absorbing glass and a near-infrared cut filter. [Background technology]

[0002] In recent years, compact cameras such as smartphones do not simply digitize the image information obtained, but also reconstruct the image by performing various computational processes on the image information. For example, it has become mainstream to extract a specific object and adjust the color and contrast of the image. In this case, if color information that does not actually exist is input to the image sensor due to the reflection of light in the optical element, that information must be removed, which is undesirable.

[0003] The near-infrared cut filter has a function of cutting out unnecessary near-infrared light (wavelengths of 700 to 1200 nm) in the wavelength sensitivity range of the image sensor. The near-infrared cut filter is generally provided immediately before the image sensor.

[0004] As the near-infrared cut filter, one that uses near-infrared absorbing glass as a substrate and is polished into a flat plate is widely used.

[0005] Near-infrared absorbing glass generally contains Cu ions. An example of the spectral transmittance characteristics of near-infrared absorbing glass is shown in FIG. 1. Note that FIG. 1 does not limit the present invention in any way. The light absorption characteristics in the vicinity of wavelengths of 700 to 1200 nm are due to the presence of Cu ions (Cu 2+ ) is expressed by the presence of Cu ions (Cu ions). 2+ ) can exhibit the near-infrared absorption characteristics over a wide wavelength range, making it useful as glass for near-infrared cut filters (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-12630 A

[0007] In the transmittance curve for wavelengths of 600 nm and above in Figure 1, the wavelength at which the transmittance is 50% is called the "half value" and is one of the main standards for near-infrared cut filters. The half value varies depending on the filter specifications, but is often set to a wavelength range of 600 nm to 650 nm. A common method for setting the half value to a desired value is to follow the Beer-Lambert law and adjust the thickness of the glass substrate or the concentration of Cu ions (Cu 2+ ) There are ways to adjust either the concentration. Summary of the Invention [Problem to be solved by the invention]

[0008] A near-infrared cut filter is required to have an excellent ability to cut near-infrared rays (that is, low transmittance of near-infrared light while having a desired half-value), as well as high transmittance in the visible range (purple to red range).

[0009] In recent years, imaging element modules mounted on smartphones and other devices are required to be both compact and high-performance, and the near-infrared cut filters are required to be thinner. Therefore, the thickness of near-infrared absorbing glass has been reduced from the conventional 1 mm to around 0.45 mm, 0.3 mm, or 0.2 mm in recent years, and further reduction to the 0.1 mm range is also desired.

[0010] Simply thinning the near-infrared absorbing glass reduces the optical density (molar number x thickness) of CuO required for near-infrared absorption, resulting in a decrease in near-infrared absorption efficiency. Increasing the amount of CuO is considered as a solution to this problem. However, simply increasing the amount of CuO leads to absorption of CuO in the visible range around 600 nm in wavelength (i.e., the red range), and the transmittance on the short wavelength side also tends to decrease, making it difficult to maintain both the transmittance in the visible range (purple to red range) and near-infrared absorption.

[0011] Furthermore, in order to provide a near-infrared absorbing glass that is suitable for use in a high-temperature, high-humidity environment, it is desirable that the deterioration of weather resistance in the high-temperature, high-humidity environment is suppressed. However, according to the study by the present inventors, it is not easy to suppress the deterioration of weather resistance while maintaining both the transmittance in the visible range (purple to red regions) and the near-infrared absorption.

[0012] In view of the above, an object of one aspect of the present invention is to provide a near-infrared absorbing glass that has high transmittance in the visible region (purple region to red region) even when made thin, has excellent near-infrared cutting ability, and is capable of suppressing deterioration in weather resistance, and a near-infrared cut filter made of such near-infrared absorbing glass. [Means for solving the problem]

[0013] One aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; The total content of B2O3 and SiO2 (B2O3+SiO2) is 3.0% or less, CuO content is α1% or more, α1 is expressed by the following formula 1: (Formula 1) α1=70400×exp(-2.855×R) is a value calculated by In the above formula 1, R is the ratio (O ions / P ions) Near infrared absorbing glass (hereinafter also referred to as "glass 1"), Regarding.

[0014] Another aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; The total content of B2O3 and SiO2 (B2O3+SiO2) is 3.0% or less, Formula 2 below: (Formula 2) C-3200×exp(-2.278×R)≧0 Fulfilling In the above formula 2, C is the CuO content per molar volume of the glass (unit: mmol / cc), R is the ratio (O ions / P ions) Near infrared absorbing glass (hereinafter also referred to as "glass 2"), Regarding.

[0015] Another aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; Formula 3 below: (Formula 3) A1 = {O(P)-O(others)} × Cu A calculated by is 2500 or more, In the above formula 3, O(P) represents the amount of oxygen that constitutes the oxide of P ion in the oxide-based glass composition, O(others) represents the amount of oxygen obtained by subtracting the above O(P) from the amount of oxygen constituting the oxides of the above major cations in the oxide-based glass composition, Cu indicates the molar CuO content in the glass composition based on oxides. Near infrared absorbing glass (hereinafter also referred to as "glass 3"); Regarding.

[0016] Another aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; Formula 4 below: (Formula 4) A2={O(P)-O(others)}×C A2 calculated by is 700 or more, In the above formula 4, C is the CuO content per molar volume of the glass (unit: mmol / cc), O(P) represents the amount of oxygen that constitutes the oxide of P ion in the oxide-based glass composition, O(others) indicates the amount of oxygen obtained by subtracting the above O(P) from the amount of oxygen constituting the oxides of the above main cations in the glass composition based on oxides. Near infrared absorbing glass (hereinafter also referred to as "glass 4"). Regarding.

[0017] One aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; CuO content is α2% or more, α2 is calculated using the following formula 5: (Formula 5) α2 = (76522) × exp(-2.855 × R) is a value calculated by In the above formula 5, R is the ratio (O ions / P ions) Near infrared absorbing glass (hereinafter also referred to as "glass 5"); Regarding.

[0018] Another aspect of the present invention is Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, The ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less, In the glass composition shown in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the above main cations is 90.0% or more, The total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, the ratio of the sum of the Na2O content, the K2O content and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less; Formula 6 below: (Formula 6) C-(3478)×exp(-2.278×R)≧0 Fulfilling In the above formula 6, C is the CuO content per molar volume of the glass (unit: mmol / cc), R is the ratio (O ions / P ions) Near infrared absorbing glass (hereinafter also referred to as "glass 6"), Regarding. Effect of the Invention

[0019] According to one aspect of the present invention, it is possible to provide a near-infrared absorbing glass that has high transmittance in the visible region (purple region to red region) even when thinned, has excellent near-infrared blocking ability, and is capable of suppressing deterioration in weather resistance. Furthermore, according to another aspect of the present invention, it is possible to provide a near-infrared cut filter made of such near-infrared absorbing glass. [Brief description of the drawings]

[0020] [Figure 1] 2 shows an example of the spectral transmittance characteristics of near-infrared absorbing glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] [Near infrared absorbing glass] Hereinafter, Glasses 1 to 6 are collectively referred to simply as “glass” or “near infrared absorbing glass.” Unless otherwise specified, the descriptions regarding the glass composition and physical properties apply to all of Glasses 1 to 6.

[0022] In the present invention and this specification, the near infrared absorbing glass is a glass having a property of absorbing light in at least the entire region or part of the wavelengths in the near infrared wavelength range (wavelengths of 700 to 1200 nm). Moreover, the near infrared absorbing glass according to one embodiment of the present invention can be an oxide glass since it contains O ions as a constituent ion. The oxide glass is a glass in which the main network forming component of the glass is an oxide. Furthermore, the near infrared absorbing glass according to one embodiment of the present invention can be a phosphate glass since it contains P ions (cations) as well as O ions (anions) as constituent ions. The O ions are anions of oxygen atoms, and are generally also called oxide ions.

[0023] Glasses 1 to 6 will be described in more detail below.

[0024] <Glass composition> (Analysis method) Regarding the various components constituting the glass, the contents of elements contained in the glass (mass % of elements) can be quantified by known methods such as inductively coupled plasma atomic emission spectrometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS). The anion components contained in the glass can be identified and quantified by known analytical methods such as ion chromatography and non-dispersive infrared absorption (ND-IR) methods. In the present invention and this specification, the content of a component being 0% or not being contained or not being introduced means that the component is substantially not contained, and it is acceptable for the component to be contained at an unavoidable impurity level.

[0025] (Glass composition based on oxides) Based on the results of the above analysis, the content (unit: mol%) of each component in the glass composition based on oxides can be calculated. The specific method is as follows. The content of element i obtained by the above analytical method (mass%P i ) to the atomic weight M of element i i By dividing by n, the number of moles of each element is i =P i / M i Request. The above element i is cationic component A i If so, the number of moles of the element obtained above, n i the mole number of the corresponding oxide n' i Specifically, the cationic component A corresponding to element i is i The formula of the oxide is A i When expressed as xOy, n' i =n i / x. The above element i is an anion component B other than O ion. i The number of moles of the corresponding element n i From now on, i It is written as follows. Cationic component A in the glass composition based on oxides i Oxide A i Content of PA as xOy i (mol%) is PA i =n' i / (Σn' i +Σm i ) x 100 The content in the glass composition based on oxides can also be referred to as the oxide based fraction.

[0026] In the oxide-based glass composition, anion components other than O ions B i Oxide base fraction PB i (mol%) is PB i =m i / (Σn' i +Σm i ) x 100 It is expressed as:

[0027] Here, Σn' i is the oxide A of the cationic component contained in the glass. i The sum of the moles of xOy. However, depending on the significant figures of the content, ignoring trace amounts of components will not affect the calculation results.

[0028] (anion%) "Anion %" is a value calculated by "(content of anion of interest i, expressed in mol %) / (total number of anions contained in glass, expressed in mol %)×100", and means the molar percentage of the amount of anion of interest relative to the total amount of anions. The anion % of O ions based on the above description of the oxide-based glass composition is: Cationic component A corresponding to element i i The formula of the oxide is A i xOy, and the cationic component A i The number of O contained in the oxide of the cation component A i Oxide standard fraction PA i (mol%) i =PA i xy, anion component B k The valence of N k , and then (ΣO i -Σ(N k / 2)B k ) / (ΣO i -Σ(N k / 2)B k +ΣB k ) x 100 It can be calculated as: Here, ΣO i is the sum of the moles of O ions in the oxide-based glass composition, and Σ(N k / 2)B k is the anion component B k represents the number of moles of O ions replaced by the numerator (ΣO i -Σ(N k / 2)B k ) is the number of moles of O ions contained in the glass. On the other hand, in the present invention and this specification, when no anion components other than oxygen are detected by analysis using a known method, all of the anion components (i.e., 100 anion %) are deemed to be O ions with regard to the oxygen content.

[0029] (cationic component) The formal valence of each cation is used to determine the valence of the cationic component. The formal valence is the valence required for an oxide of a given cation to maintain electrical neutrality when the valence of the O ion that constitutes the oxide is set to -2, and can be determined uniquely from the chemical formula of the oxide. For example, for Cu ions, the O 2- To maintain electrical neutrality between and Cu, the valence of Cu is +2. For example, for P ions, the O 2- To maintain electrical neutrality between A and P, the valence of P is +2×5 / 2=+5. Generalizing this, the formal valence of the cation Ai contained in the oxide AixOy is +2y / x. Therefore, when analyzing the glass composition, it is not necessary to analyze the valence of the cation. In addition, the valence of an anion (for example, the valence of O ion is -2) is a formal valence based on the idea that O ions accept two electrons and form a closed shell structure. Therefore, when analyzing glass composition, it is not necessary to analyze the valence of an anion. 2+ A part of Cu is melted. + However, since the amount is usually small, the valence of all Cu can be considered to be +2.

[0030] (anion component) The above glass contains at least O ions as anions, and the content is 90.0 anion % or more in the glass composition expressed in anion %. The inventor believes that by lowering the O / P ratio in a glass mainly containing O ions as anions in this way, the absorption in the red region of CuO can be shifted to the long wavelength side, and the content of CuO can be increased without decreasing the transmittance in the red region, thereby improving the near infrared ray cutting ability. The O ion content in the glass composition expressed in anion % is 90.0% or more, preferably 95.0% or more, more preferably 98.0% or more, and even more preferably 99.0% or more. A high ratio of O ions in the anion components is also preferable in terms of suppressing volatilization during glass melting. Suppressing volatilization during glass melting is preferable from the viewpoint of suppressing the occurrence of striae. In particular, from the viewpoint of suppressing volatilization during glass melting, increasing productivity, and suppressing the generation of harmful gases during production, the content of O ions is preferably 100%. The formal valence of O ions is -2.

[0031] In one embodiment, the glass may contain only O ions as anions, and in another embodiment, the glass may contain O ions and one or more other anions. Examples of the other anions include F ions, Cl ions, Br ions, and I ions. The formal valence of F ions, Cl ions, Br ions, and I ions is -1.

[0032] From the viewpoints of improving the homogeneity and strength of the glass, the content of F ions in the glass composition expressed in anion % is preferably 15.0 anion % or less, more preferably 10.0 anion % or less, even more preferably 5.0 anion % or less, even more preferably 2.0 anion % or less, and even more preferably 1.0 anion % or less. In particular, from the viewpoints of suppressing volatilization during glass melting, increasing productivity, and suppressing the generation of harmful gases during production, the above glass may be glass that does not contain F ions.

[0033] (O / P ratio) The molar ratio of the cation content to the anion content is the ratio of the contents (in mol%) of the components of interest when the total amount of all cationic components and all anionic components is 100 mol%. Therefore, the ratio of the O ion content to the P ion content (O ion / P ion) is the ratio of the O ion content (in mol%) to the P ion content (in mol%) when the total amount of all cationic components and all anionic components is 100 mol%.

[0034] O / P ratio calculation method 1 Regarding the O / P ratio (also expressed as R), the O / P ratio based on the above explanation of the notation of the oxide-based glass composition is as follows: Cationic component A corresponding to element i i The formula of the oxide is A i The number of O contained in the oxide of the cationic component Ai is expressed as O x O y using the oxide base fraction PAi (mol%) of the cationic component Ai. i =PA i xy, anion component B k The valence of N k , and then Formula D1: R1=ΣO i -Σ(N k / 2)B k Equation D2: R2 = oxide of P ion (i.e. P2O5) basis fraction (mol%) x 2 O / P ratio (R) is Formula D3: R=R1 / R2 It can be found from. For example, taking Comparative Example A described later as an example, the contents in the glass composition based on oxides in Comparative Example A, expressed as mole percent values, are P2O5=53.59, Li2O=19.30, and CuO=27.11. The number of O atoms contained in the molecular formula is 5 for P2O5, 1 for Li2O, and 1 for CuO. The number of moles of O contained in the molecular formula is 267.95 for P2O5, 19.30 for Li2O, and 27.11 for CuO. The O / P ratio of the glass in this example can be determined as follows. The number of O ions in the molecular formula of glass: 53.59P2O5-19.30Li2O-27.11CuO, N S The molecular formula of glass is the compositional formula of glass expressed so that the total number of molecules contained in the glass is 100. That is, using the number of O ions contained in the molecular formula of each oxide MxOy (P2O5:5, Li2O:1, CuO:1), N S =53.59×5+19.30×1+27.11×2=314.36 As N S Calculate. In the above example glass, there are zero O ions replaced by other anions in the molecular formula of the glass. S Dividing O / P ratio = 314.36 by the number of moles of P contained in P2O5, 53.59 x 2, gives us the O / P ratio = 314.36 / (53.59 x 2) = 2.93...

[0035] O / P ratio calculation method 2 When one or more other anion components are detected in addition to oxygen by analysis using a known method, the oxygen content can be calculated from (1) the cation content based on the valences of the cationic components contained in the glass and the mole % of the elements, and (2) the anion content based on the valences of the anion components other than oxygen and the mole % of the elements using the method in (3) below (unit: anion %). That is, from the results of identification and quantitative analysis by known methods, (1) Regarding the cationic components contained in the glass, the total U is calculated as "the cationic content based on the number of oxygen atoms per cation (y / x) × the mole percent of the element, where y is the number of oxygen atoms in the oxide MxOy and x is the number of cations." (2) For the anion components excluding oxygen, the sum V of "anion content based on the mole percent of the element x number of oxygen atoms substituted per anion z / 2" is calculated from the results of identification and quantitative analysis by known methods and the valence z of the anion. (3) UV can also be taken as the ratio of O ion content to P ion content.

[0036] As calculation examples of Calculation Method 2, the following Calculation Example 1 and Calculation Example 2 are shown.

[0037] Calculation example 1: When the mole percentages of the elements P ion, Li ion, and Cu ion are quantified as 22.0, 8.0, and 5.5 (contents expressed in mole percent of the elements), the y / x of the corresponding oxides: P2O5, Li2O, and CuO are 2.5, 0.5, and 1.0, respectively. U = 22 x 2.5 + 8 x 0.5 + 5.5 x 1.0 = 64.5. V=0. Therefore, the molar percentage of O ions based on the molar percentage of the element is 64.5 (content of the element expressed in molar percentage). From the ratio of the O ion value thus determined and the mole percentage of the analyzed P ions, the O / P ratio = 64.5 / 22 = 2.93... can be calculated.

[0038] Calculation Example 2: When the mole percentages of the elements P, Li, and Cu ions are quantified as 22.0, 8.0, and 5.5 (contents expressed in mole percent of the elements), and the mole percentage of the element F ion is 4.0 (contents expressed in mole percent of the elements), the y / x of the corresponding oxides P2O5, Li2O, and CuO are 2.5, 0.5, and 1.0, respectively, and the valence of F is -1, so U = 22 x 2.5 + 8 x 0.5 + 5.5 x 1.0 = 64.5. V = 4 × 1 / 2 = 2. Therefore, the molar percentage of O ions based on the molar percentage of the element is 62.5 (content of the element expressed in molar percentage). From the ratio of the O ion value thus determined and the mole percentage of the analyzed P ions, the O / P ratio = 62.5 / 22 = 2.84... can be calculated.

[0039] In Glasses 1 to 6, from the viewpoint of achieving both improved transmittance in the visible range and improved near-infrared blocking ability, as well as from the viewpoint of improving the thermal stability of the glass, the ratio of the O ion content to the P ion content (O / P ratio) is 3.15 or less. In Glasses 1 to 6, the O / P ratio is preferably 3.14 or less, and more preferably 3.13 or less, 3.12 or less, 3.11 or less, 3.10 or less, 3.09 or less, 3.08 or less, 3.07 or less, 3.06 or less, 3.05 or less, 3.04 or less, 3.03 or less, 3.02 or less, 3.01 or less, and 3.00 or less, in that order. On the other hand, from the viewpoint of improving weather resistance and / or suppressing a decrease in meltability, a large O / P ratio is preferable in Glasses 1 to 6. From this viewpoint, the O / P ratio in Glasses 1 to 6 is preferably 2.50 or more, and is more preferably 2.60 or more, 2.65 or more, 2.70 or more, 2.73 or more, 2.75 or more, 2.77 or more, 2.80 or more, 2.81 or more, 2.82 or more, 2.83, 2.84 or more, 2.85 or more, 2.86 or more, 2.87 or more, 2.88 or more, 2.89 or more, and 2.90 or more, in that order.

[0040] (cationic component) Glasses 1 to 6 contain four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions, and contain P ions, Li ions, and Cu ions as essential cations. In the oxide-based glass composition (molar basis) of glasses 1 to 6, the total content of oxides of the above major cations is 90.0% or more. In glasses 1 to 6, the total content of oxides of the main cations being 90.0% or more can contribute to improving the thermal stability of the glass and / or to improving the optical homogeneity of the glass by suppressing striae, volatilization, etc. From the above viewpoints, the total content of oxides of the main cations in glasses 1 to 6 is preferably 92.0% or more, more preferably 93.0% or more, 95.1% or more, 96.1% or more, 97.1% or more, 98.1% or more, 98.6% or more, 99.1% or more, and 99.6% or more in that order, and can also be 100%. In one embodiment, the total content of oxides of the main cations in glasses 1 to 6 can be 100% or less, 99.5% or less, 99% or less, 98.5% or less, 98.0% or less, or 97.5% or less.

[0041] Hereinafter, the content of the cationic component will be described as the content in the glass composition based on oxides (based on molar basis).

[0042] Since CuO is an essential component for imparting near-infrared cutting ability to glass, Glasses 1 to 6 contain Cu ions as essential cations.

[0043] In Glass 1, the CuO content is α1% or more. α1 is a value calculated by the following formula 1.

[0044] (Formula 1) α1=70400×exp(-2.855×R)

[0045] In Equation 1, R is the O / P ratio.

[0046] For glass 2, the lower limit of the CuO content is defined by the CuO content per molar volume of the glass, as given by the following formula 2.

[0047] (Formula 2) C-3200×exp(-2.278×R)≧0

[0048] In Equation 2, C is the CuO content per molar volume of the glass (units: mmol / cc) and R is the O / P ratio.

[0049] In the formula 2, C can be determined by the following method. C is calculated by measuring the specific gravity D (g / cc) of the glass, calculating the mass equivalent to 1 mole of the glass composition, i.e., the molar molecular weight M (g / mol), based on the glass composition obtained by the analysis as described above, and calculating the molar volume M / D of the glass (unit: cc / mol). C = mole % of CuO / (M / D) x 1000 (unit: millimoles / cc) It can be calculated as follows: The molar molecular weight M is Based on the above description of the glass composition based on oxides, the formula weight MA of the corresponding oxide of the above cationic component Ai i , anion component B k The atomic weight of MB k , and the atomic weight of oxygen is Mo, M = {Σ(PA i ×MA i )+Σ(PB k ×MB k )-Σ(N k / 2)Mo} / ΣPA i It can be calculated as: For example, if the glass composition is composed of s mol% A2O component on an oxide basis, t mol% BO component on an oxide basis, and u mol% F component, and s+t+u=100(%), the formula weight of the A2O component is M A (g / mol), the formula weight of the BO component is M B (g / mol), the atomic weight of F is M F (g / mol), the atomic weight of oxygen is M O (g / mol), where M = (s × M A +t×M B +u×M F -u / 2×M O ) / (s+t) It becomes. For example, the molar molecular weight M of Comparative Example A described later (the contents in mole percent in the glass composition based on oxides are P2O5=53.59, Li2O=19.30, and CuO=27.11) is: Formula weight of P2O5: 141.94 (g / mol) Formula weight of Li2O: 29.88 (g / mol) Formula weight of CuO: 79.55 (g / mol) Using this, we can calculate that M = (53.59 × 141.94 + 19.30 × 29.88 + 27 11 × 79.55) / (53.59 + 19.30 + 27.11) = 103.40 (g / mol).

[0050] As a result of intensive research, the inventors have newly discovered that, in a glass mainly composed of O ions as an anion, when the O / P ratio is decreased, the absorption in the red region of CuO shifts to the long wavelength side, thereby suppressing the decrease in the transmittance in the red region and increasing the CuO content. Furthermore, the inventors have newly discovered that there is a good correlation between the O / P ratio and the CuO content for achieving a predetermined half value at a predetermined thickness, and have come to define the lower limits of the CuO content (α1, α2) by Formula 1 for Glass 1 having an O / P ratio in the above-described range, and by Formula 5 for Glass 5. In addition, the inventors have come to define the CuO content per molar volume of the glass by Formula 2 for Glass 1 having an O / P ratio in the above-described range, and by Formula 6 for Glass 6.

[0051] In glass 3, the CuO content is defined based on A1 calculated by the following formula 3, and A1 is 2500 or more.

[0052] (Formula 3) A1 = {O(P)-O(others)} × Cu

[0053] In formula 3, O(P) represents the amount of oxygen constituting the oxide of P ion in the oxide-based glass composition, O(others) represents the amount of oxygen obtained by excluding the above O(P) from the amount of oxygen constituting the oxide of the main cation listed above for Glass 3 in the oxide-based glass composition, and Cu represents the molar CuO content in the oxide-based glass composition.

[0054] “O(P)” in Equation 3 is calculated as follows: When the P2O5 content in the oxide-based glass composition (molar basis) is M mole %, the number of oxygen atoms in the chemical formula of P2O5 is 5, and O(P) is calculated as "O(P) = M × 5". Similarly, for major cations other than P ions, the amount of oxygen constituting the oxide of each cation is calculated using the content value as the oxide in the oxide-based glass composition (molar basis) and the number of oxygen atoms contained in the oxide formed by each cation in the formal valence state. In this way, “O(others)” is calculated as the sum of the oxygen amounts calculated for the oxides of the major cations minus O(P). When the CuO content in the oxide-based glass composition (molar basis) is N mol %, “A” is calculated as A1={O(P)−O(others)}×N.

[0055] As described above, the present inventors have newly discovered that, in a glass mainly composed of O ions as an anion, when the O / P ratio is reduced, the absorption in the red region of CuO shifts to the long wavelength side, thereby suppressing the decrease in the transmittance in the red region and increasing the CuO content. Furthermore, the inventors have newly discovered that, by configuring the chemical species other than PO coordinated to CuO with a chemical species having a smaller ionic radius and a smaller valence, the transmittance in the visible region (purple region to red region) can be increased as a result by the following 1) and 2). Based on this discovery, the CuO content of glass 3 is specified based on A calculated by formula 3. 1) Cu 2+ By shifting the absorption due to this to a longer wavelength, the transmittance in the red region can be increased. 2) By making it possible to turn glass into a liquid phase at low temperatures, Cu, which absorbs light in the purple region around 400 nm in wavelength, + The occurrence of the above problems can be suppressed.

[0056] With regard to glass 3, from the viewpoint of achieving both improved transmittance in the visible range and improved near-infrared blocking ability, A1 is 2500 or more, and preferably 2800 or more, and more preferably 2900 or more, 3000 or more, 3100 or more, 3200 or more, 3300 or more, 3400 or more, 3500 or more, 3600 or more, 3700 or more, 3800 or more, 3900 or more, 4000 or more, 4100 or more, 4200 or more, 4300 or more, 4400 or more, 4500 or more, 4600 or more, 4700 or more, 4800 or more, 4900 or more, 5000 or more, 5100 or more, 5200 or more, 5300 or more, 5400 or more, 5500 or more, 5600 or more, 5700 or more, 5800 or more, 5900 or more, 5800 or more, 5900 or more, 6000 or more, 6100 or more, 6200 or more, 6300 or more, 6400 or more, 6500 or more, 6600 or more, 6700 or more, 6800 or more, 6900 or more, 7000 or more, 7100 or more, 7200 or more, 7300 or more, 7400 or more, 7500 or more, 7600 or more, 7700 or more, 7800 or more, 7900 or more, 8000 or more, 8100 or more, 8200 or more, 8300 or more, The following are more preferred in order: 300 or more, 4400 or more, 4500 or more, 4600 or more, 4700 or more, 4800 or more, 4900 or more, 5000 or more, 5100 or more, 5200 or more, 5300 or more, 5400 or more, 5500 or more, 5600 or more, 5700 or more, 5800 or more, 5900 or more, 6000 or more, 6100 or more, 6200 or more, 6300 or more, 6400 or more, and 6500 or more. On the other hand, from the viewpoint of further suppressing the decrease in thermal stability of the glass due to the inclusion of a large amount of Cu and O, the decrease in transmittance at a desired half-value wavelength, and / or the decrease in thermal stability or the decrease in weather resistance of the glass due to an insufficient amount of O(others), A is preferably 20000 or less, more preferably 19000 or less, 18000 or less, 17000 or less, 16000 or less, 150000 or less, 14000 or less, 13000 or less, 12000 or less, 11000 or less, 10000 or less, 9000 or less, or 8000 or less. Note that, in order to achieve the desired half-value with a thinner wall thickness, this value tends to be larger.

[0057] In glass 4, the CuO content is defined based on A2 calculated by the following formula 4, and A2 is 700 or more.

[0058] (Formula 4) A2={O(P)-O(others)}×C

[0059] In formula 4, C is the CuO content per molar volume of the glass (unit: mmol / cc), O(P) is the amount of oxygen constituting the oxide of P ion in the oxide-based glass composition, and O(others) is the amount of oxygen excluding the O(P) from the amount of oxygen constituting the oxide of the above-mentioned major cations in the oxide-based glass composition.

[0060] Regarding glass 4, from the viewpoint of achieving both improved transmittance in the visible range and improved near-infrared cutoff capability, A2 is 700 or more, preferably 800 or more, more preferably 850 or more, 890 or more, 1000 or more, 1100 or more, 1200 or more, 1300 or more, 1400 or more, 1500 or more, 1600 or more, 1700 or more, and 1800 or more in that order. On the other hand, from the viewpoint of further suppressing the decrease in thermal stability of the glass due to the inclusion of a large amount of Cu and O, the decrease in transmittance at a desired half-value wavelength, and / or the decrease in thermal stability or the decrease in weather resistance of the glass due to an insufficient amount of O(others), A2 is preferably 5000 or less, more preferably 4000 or less, 3500 or less, 3000 or less, 2500 or less, and 2000 or less. Note that in order to achieve a desired half-value transmittance with a thinner wall thickness, this value tends to be larger.

[0061] Furthermore, the CuO content is α2% or more in Glass 5. α2 is a value calculated from the following formula 5.

[0062] (Formula 5) α2=76522×exp(-2.855×R)

[0063] In Equation 5, R is the O / P ratio.

[0064] For glass 6, the lower limit of the CuO content is defined by the CuO content per molar volume of the glass, as given by the following formula 6.

[0065] (Formula 6) C-3478×exp(-2.278×R)≧0

[0066] In Equation 6, C is the CuO content per molar volume of the glass (units: mmol / cc) and R is the O / P ratio.

[0067] The CuO content of Glasses 1 to 6 is preferably 4.0% or more in the glass composition based on oxides (molar basis), and more preferably in this order: 5.0% or more, 6.0% or more, 7.0% or more, 7.5% or more, 8.0% or more, 8.5% or more, 9.0% or more, 9.5% or more, 10.0% or more, 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more. From the viewpoint of leaving room for the introduction of glass-forming components and maintaining the thermal stability of the glass, the CuO content is preferably 48.0% or less, and further preferably 47.0% or less, 46.0% or less, 45.0% or less, 44.0% or less, 43.5% or less, 43.0% or less, 42.5% or less, 42.0% or less, 41.5% or less, 41.0% or less, 40.5% or less, 40. The order of preference is 0% or less, 39.5% or less, 39.0% or less, 38.5% or less, 38.0% or less, 37.5% or less, 37.0% or less, 36.5% or less, 36.0% or less, 35.5% or less, 35.0% or less, 34.5% or less, 34.0% or less, 33.5% or less, 33.0% or less, 32.5% or less, 32.0% or less, 31.5% or less, and 31.0% or less.

[0068] The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.11 mm T In order for 50 to be in the range of 600 nm to 650 nm, the CuO content is preferably 15.0% or more in the glass composition based on oxides (molar basis), and more preferably in this order 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.21 mm is T In order for 50 to be in the range of 600 nm to 650 nm, the CuO content is preferably 10.0% or more in the glass composition based on oxides (molar basis), and more preferably in this order: 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.25 mm T In order for 50 to be in the range of 600 nm to 650 nm, the CuO content is preferably 10.0% or more in the glass composition based on oxides (molar basis), and more preferably in this order: 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more. On the other hand, the transmittance characteristics converted to a thickness of 0.25 mm are as follows: when the CuO content is large, the wavelength λ at which the external transmittance including reflection loss becomes 50%. T 50 may be less than 600 nm, and therefore the CuO content is preferably 35.0% or less, and more preferably in this order: 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.5% or less, 29.0% or less, 28.5% or less, 28.0% or less, 27.5% or less, 27.0% or less, 26.5% or less, 26.0% or less, 25.5% or less, 25.0% or less, 24.5% or less, 24.0% or less, 23.5% or less, 23.0% or less, 22.5% or less, 22.0% or less, 21.5% or less, 21.0% or less, 20.5% or less, and 20.0% or less. The wavelength λ at which the external transmittance including reflection loss becomes 50% at wavelengths of 550 nm or moreT In order for the thickness of the glass in which .gamma.-50 is 645 nm to be 0.25 mm or less, the CuO content is preferably 10.0% or more in the oxide-based glass composition (molar basis), and more preferably in this order: 10.5% or more, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% at wavelengths of 550 nm or more T In order for the thickness of the glass in which .gamma.-50 is 633 nm to be 0.25 mm or less, the CuO content is preferably 10.5% or more in the oxide-based glass composition (molar basis), and more preferably in this order: 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, 13.0% or more, 13.5% or more, 14.0% or more, 14.5% or more, 15.0% or more, 15.5% or more, 16.0% or more, 16.5% or more, 17.0% or more, 17.5% or more, 18.0% or more, 18.5% or more, 19.0% or more, 19.5% or more, and 20.0% or more.

[0069] In glasses 2 and 4, the value of C is preferably 3.0 or more, and more preferably in the following order: 3.1 or more, 3.3 or more, 3.5 or more, 3.7 or more, 3.9 or more, 4.0 or more, 4.1 or more, 4.2 or more, 4.3 or more, 4.4 or more, 4.5 or more, 4.6 or more, 4.7 or more, 4.8 or more, 4.9 or more, 5.0 or more, 5.1 or more, 5.2 or more, 5.3 or more, and 5.4 or more and 5.5 or more. From the viewpoint of leaving room for the introduction of glass-forming components and maintaining the thermal stability of the glass, the value of C is preferably 16.0 or less, and further preferably 15.0 or less, 14.0 or less, 13.5 or less, 13.0 or less, 12.5 or less, 12.0 or less, 11.9 or less, 11.8 or less, 11.7 or less, 11.6 or less, 11.5 or less, 11.4 or less, 11.3 or less, 11.2 or less, 11.1 or less, 11.0 or less. The more preferable ranges are 10.9 or less, 10.8 or less, 10.7 or less, 10.6 or less, 10.5 or less, 10.4 or less, 10.3 or less, 10.2 or less, 10.1 or less, 10.0 or less, 9.9 or less, 9.8 or less, 9.7 or less, 9.6 or less, 9.5 or less, 9.4 or less, 9.3 or less, 9.2 or less, 9.1 or less, 9.0 or less, 8.9 or less, 8.8 or less, 8.7 or less, 8.6 or less, and 8.5 or less, in that order.

[0070] In Glasses 1 to 6, the CuO content can be α3% or more, where α3 is a value calculated from the following formula 7.

[0071] (Formula 7) α3=(70400×0.25 / d)×exp(-2.855×R)

[0072] In formula 7, R is the O / P ratio. d can have a value of more than 0 and not more than 0.25. For example, d can be 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, etc. However, the value of d is not limited to these. In order to achieve a desired half-value transmittance with a thinner wall thickness, a smaller value of d tends to be preferable.

[0073] For example, when d=0.11, the CuO content can be α3% or more, where α3 is calculated by the following formula: α3=(70400×0.25 / 0.11)×exp(-2.855×R)

[0074] When the glass has an external transmittance of 50% for light having a wavelength of 633 nm, and the thickness of the glass is D (mm), in one embodiment, d in the above formula 7 can be D. In this case, α3 is calculated by the following formula. α3=(70400×0.25 / D)×exp(-2.855×R)

[0075] For glasses 1 to 6, the lower limit of the CuO content may be a value defined by the following formula 8 based on the CuO content per molar volume of the glass.

[0076] (Formula 8) C-3200×0.25 / d×exp(-2.855×R)≧0

[0077] In formula 8, d can take a value of more than 0 and not more than 0.25. For example, d can be 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, etc. However, the value of d is not limited to these. In order to achieve a desired half-value transmittance with a thinner wall thickness, a smaller value of d tends to be preferable.

[0078] For example, when d=0.11, Equation 8 becomes the following equation. C-3300×0.25 / 0.11×exp(-2.855×R)≧0

[0079] When the thickness of the glass when the external transmittance of the glass for light having a wavelength of 633 nm is 50% is D (mm), in one embodiment, d in the above formula 8 can be equal to D. In this case, formula 8 is as follows:

[0080] With respect to CuO content, glasses 1-6 may each also satisfy one or more of the provisions of the formula for the other glasses.

[0081] Glasses 1 to 6 contain P ions as essential cations. As described above, from the viewpoint of achieving both improved transmittance in the visible range and improved near-infrared blocking capability, it is preferable that the O / P ratio is low. In order to reduce the O / P ratio, it is preferable to increase the P2O5 content. From this point of view, the P2O5 content in the glass composition based on oxides (by mole) is preferably 33.0% or more, and more preferably in the following order: 34.0% or more, 35.0% or more, 36.0% or more, 37.0% or more, 38.0% or more, 39.0% or more, 40.0% or more, 40.5% or more, 41.0% or more, 41.5% or more, 42.0% or more, 42.5% or more, 43.0% or more, 43.5% or more, 44.0% or more, 44.5% or more, 45.0% or more, 45.5% or more, 46.0% or more, 46.5% or more, 47.0% or more, 47.5% or more, 48.0% or more, 48.5% or more, 49.0% or more, 49.5% or more, and 50.0% or more. Since P2O5 itself is a component that does not have near-infrared absorbing ability, from the viewpoint of increasing the CuO content having near-infrared absorbing ability, the P2O5 content is preferably 72.0% or less, more preferably 71.0% or less, 70.0% or less, 69.5% or less, 69.0% or less, 68.5% or less, 68.0% or less, 67.5% or less, 67.0% or less, 66.5% or less, 66.0% or less, 65.5% or less, 65.0% or less, 64.5% or less, 64.0% or less, 63.5% or less, 63.0% or less, 62.5% or less, 62.0% or less, 61.5% or less, 61.0% or less, 60.5% or less, and 60.0% or less in that order. In addition, it is preferable that the P2O5 content is less than the above value from the viewpoint of further suppressing the deterioration of weather resistance and / or suppressing the deterioration of meltability.

[0082] In order to obtain the desired transmittance characteristics, it is desirable that the glass composition based on oxides is mainly composed of P2O5, Li2O, and CuO. From this point of view, the total content of P2O5, Li2O, and CuO (P2O5+Li2O+CuO) is preferably 50.0% or more, and more preferably 55.0% or more, 60.0% or more, 65.0% or more, 70.0% or more, 75.0% or more, 80.0% or more, 83.0% or more, 86.0% or more, 88.0% or more, and 90.0% or more in that order. The above glass contains P ions, Li ions, and Cu ions as essential cations, and further contains one or more cations selected from the group of major cations in order to obtain the thermal stability and / or chemical durability of the glass. Therefore, the total content (P2O5+Li2O+CuO) is less than 100%, and is preferably 9.9% or less, and more preferably 99.8% or less, 99.7% or less, 99.6% or less, 99.5% or less, 99.4% or less, 99.2% or less, 99.0% or less, 98.0% or less, 97.0% or less, 96.0% or less, 95.0% or less, 94.0% or less, 93.0% or less, 92.0% or less, 91.0% or less, 90.0% or less, 89.0% or less, 88.0% or less, 87.0% or less, 86.0% or less, and 85.0% or less, in that order.

[0083] In one form, the transmittance characteristic converted to a thickness of 0.11 mm is the wavelength λ at which the external transmittance including reflection loss becomes 50%. T In order for 50 to be in the range of 600 nm to 650 nm, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 84.0% or more, and more preferably 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more in that order. The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.21 mm T 50 is in the range of 600nm to 650nm, so P2O 5、The total content of Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 80.0% or more, and more preferably in this order: 81.0% or more, 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.25 mm T In order for 50 to be in the range of 600 nm to 650 nm, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 75.0% or more, and more preferably in this order: 76.0% or more, 77.0% or more, 78.0% or more, 79.0% or more, 80.0% or more, 81.0% or more, 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% at wavelengths of 550 nm or more T In order for the glass thickness at which .gamma.-50 is 645 nm to be 0.25 mm or less, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 80.0% or more, and more preferably in this order: 81.0% or more, 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more. The wavelength λ at which the external transmittance including reflection loss becomes 50% at wavelengths of 550 nm or more T In order for the glass thickness, at which .gamma.-50 is 633 nm, to be 0.25 mm or less, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 81.0% or more, and more preferably 82.0% or more, 83.0% or more, 84.0% or more, 85.0% or more, 86.0% or more, 87.0% or more, 88.0% or more, 89.0% or more, and 90.0% or more in that order. Examples of glasses that fall into the above-mentioned embodiment include the glasses of Examples 1 to 60 described below.

[0084] On the other hand, as another form, for glass in which the molar ratio ((MgO+CaO+SrO+BaO+ZnO) / (Li2O+Na2O+K2O)) of the total content of MgO, CaO, SrO, BaO and ZnO (MgO+CaO+SrO+BaO+ZnO) to the total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) is 2.0 or more, the wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.11 mm is T In order for 50 to be in the range of 600 nm to 650 nm, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 65.0% or more, and more preferably 66.0% or more, 67.0% or more, 68.0% or more, 69.0% or more, and 70.0% or more in that order. For the other embodiment described above, the wavelength λ at which the external transmittance including reflection loss becomes 50% is the transmittance characteristic converted to a thickness of 0.21 mm. T In order for 50 to be in the range of 600 nm to 650 nm, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 60.0% or more, and more preferably 61.0% or more, 62.0% or more, 63.0% or more, 64.0% or more, and 65.0% or more in that order. For the other embodiment described above, the wavelength λ at which the external transmittance including reflection loss becomes 50% is the transmittance characteristic converted to a thickness of 0.25 mm. T In order for 50 to be in the range of 600 nm to 650 nm, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 55.0% or more, and more preferably 56.0% or more, 57.0% or more, 58.0% or more, 59.0% or more, and 60.0% or more in that order. Regarding another embodiment of the above, the wavelength λ at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more is TIn order for the glass thickness, at which C=50 is 645 nm, to be 0.25 mm or less, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 60.0% or more, and more preferably 61.0% or more, 62.0% or more, 63.0% or more, 64.0% or more, and 65.0% or more in that order. Regarding another embodiment of the above, the wavelength λ at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more is T In order for the glass thickness, at which .gamma.-50 is 633 nm, to be 0.25 mm or less, the total content of P2O5, Li2O and CuO (P2O5+Li2O+CuO) in the glass composition based on oxides (molar basis) is preferably 61.0% or more, and more preferably 62.0% or more, 63.0% or more, 64.0% or more, 65.0% or more, and 66.0% or more in that order. Examples of glasses that fall under the above-mentioned other embodiment include Examples 61 to 66 described later.

[0085] The group of major cations described above for glasses 3 and 4 includes B ions and Si ions. On the other hand, the group of major cations described above for glasses 1, 2, 5, and 6 does not include B ions and Si ions that tend to increase the melting temperature. In one embodiment, glasses 1 to 6 may be glasses that contain one or both of B ions and Si ions that tend to shift the half-value to the short wavelength side, from the viewpoint of increasing the near-infrared cut ability of the glass and improving the transmittance in the visible range, and in another embodiment, they may be glasses that contain neither B ions nor Si ions.

[0086] For Glass 1 and Glass 2, in the glass composition based on oxides (molar basis), from the viewpoint of improving transmittance in the visible range, the total content of B2O3 and SiO2 (B2O3+SiO2) is 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less, 1.5% or less, 1.0% or less, and 0.5% or less in that order.

[0087] For Glasses 3 to 6, in terms of the glass composition based on oxides (molar basis), from the viewpoint of further improving the transmittance in the visible range, the total content of B2O3 and SiO2 (B2O3+SiO2) is preferably 3.0% or less, and more preferably 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, and 0.5% or less in that order.

[0088] In glasses 1 to 6, the total content of B2O3 and SiO2 (B2O3+SiO2) can be 0%, 0% or more, or more than 0%.

[0089] In Glasses 1 to 6, from the viewpoint of further improving the transmittance in the visible range, the B2O3 content is preferably 3.0% or less, and more preferably 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, and 0.5% or less in that order. The B2O3 content can be 0%. On the other hand, for glasses 1 to 6, when the glass is roughly melted in a quartz crucible in order to promote homogenization of the glass, the SiO2 content is preferably more than 0%, and more preferably 0.01% or more, 0.02% or more, 0.03% or more, 0.04% or more, 0.05% or more, 0.1% or more, 0.2% or more, and 0.3% or more in that order. However, the introduction of excessive SiO2 into the glass tends to reduce the optical homogeneity of the glass. From this point of view, in glasses 1 to 6, the SiO2 content is preferably 2.0% or less, and more preferably 1.4% or less, 0.9% or less, 0.8% or less, 0.6% or less, and 0.4% or less in that order.

[0090] Glasses 1 to 6 contain Li ions as an essential cation. Compared with various glass components, Li2O has a high ability to maintain the absorption of CuO in the long wavelength region, and also has a small adverse effect on weather resistance. From this viewpoint, the Li2O content is preferably 0.1% or more, and more preferably 0.5% or more, 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, 7.0% or more, 7.5% or more, and 8.0% or more in that order. On the other hand, from the viewpoint of ensuring the thermal stability of the glass and / or further suppressing and maintaining the decrease in weather resistance, the LiO content is preferably 35.0% or less, and more preferably in the following order: 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.5% or less, 29.0% or less, 28.5% or less, 28.0% or less, 27.5% or less, 27.0% or less, 26.5% or less, 26.0% or less, 25.5% or less, 25.0% or less, 24.5% or less, 24.0% or less, 23.5% or less, 23.0% or less, 22.5% or less, 22.0% or less, 21.5% or less, 21.0% or less, 20.5% or less, and 20.0% or less.

[0091] In Glasses 1 to 6, from the viewpoints of improving the meltability and improving the transmittance in the visible range, the total content of MgO and Al2O3 (MgO + Al2O3) is 8.0% or less, and preferably 7.5% or less, and more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.8% or less, 1.6% or less, 1.5% or less, and 1.4% or less, in that order, and can also be 0%. On the other hand, from the viewpoint of enhancing the weather resistance and improving the mechanical strength of the glass, the total content of MgO and Al2O3 (MgO + Al2O3) may be more than 0% and is preferably 0.1% or more, and more preferably 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1.0% or more, 1.1% or more, and 1.3% or more, in that order.

[0092] Al2O3 is a component that can particularly contribute to improving weather resistance. The Al2O3 content can be 0%, 0% or more, or more than 0%, and from the viewpoint of improving weather resistance, it is preferably 0.1% or more, and more preferably 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.9% or more, 1.1% or more, 1.3% or more, and 1.5% or more in that order. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible range, the Al2O3 content is preferably 8.0% or less, and more preferably 7.5% or less, 7.0% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, and 2.5% or less in that order. In one embodiment, from the viewpoint of prioritizing improvement of near-infrared absorption characteristics over maintenance of weather resistance of glass, and further increasing the transmittance in the visible range by suppressing a shift of the absorption of CuO to the short wavelength side, and improving the near-infrared absorption characteristics, the Al2O3 content is preferably less than 2.0%, and more preferably 1.9% or less, 1.8% or less, 1.7% or less, 1.6% or less, 1.5% or less, 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1.0% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, and 0.5% or less in that order.

[0093] MgO is a component that can be added appropriately for the reason of adjusting the thermal stability of glass, but it tends to make it difficult to increase the CuO content because it shifts the absorption of CuO to the short wavelength side. In addition, the melting property of glass tends to decrease with an increase in the MgO content. From these viewpoints, the MgO content is preferably 9.0% or less, and more preferably 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, and 2.0% or less in that order. The MgO content can be 0%. In one embodiment, from the viewpoint of improving the mechanical strength of glass, the MgO content can be more than 0%, preferably 0.5% or more, and more preferably 1.0% or more.

[0094] La2O3 is a component that can contribute to improving weather resistance without impairing the near-infrared absorption properties of glass. The La2O3 content is preferably 0.10% or more, more preferably 0.15% or more, 0.18% or more, and 0.21% or more in that order. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible range, the La2O3 content is preferably 8.0% or less, more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less in that order.

[0095] Y2O3 is also a component that can contribute to improving weather resistance without impairing the near-infrared absorption properties of glass. The Y2O3 content is preferably 0.10% or more, more preferably 0.15% or more, 0.20% or more, 0.25% or more, 0.30% or more, 0.35% or more, 0.40% or more, 0.45% or more, and 0.50% or more in this order. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible range, the Y2O3 content is preferably 8.0% or less, more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less in this order. Y2O3 can also be introduced from the viewpoint of increasing the molar volume of glass without increasing the specific gravity of glass.

[0096] Gd2O3 is also a component that can contribute to improving weather resistance. The Gd2O3 content is preferably 0.10% or more, more preferably 0.15% or more, 0.18% or more, and 0.21% or more in that order. On the other hand, from the viewpoint of further suppressing the decrease in transmittance in the visible range, the Gd2O3 content is preferably 8.0% or less, more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less in that order.

[0097] The glass composition based on oxides may or may not contain one or more rare earth oxides other than those mentioned above, such as Lu2O3, Sc2O3, etc. Since these components are generally expensive, the content of rare earth oxides other than La2O3, Y2O3, and Gd2O3 (when two or more are contained, the total content of them) is preferably 2.5% or less, more preferably 1.5% or less, 1.0% or less, 0.5% or less, and can be 0%.

[0098] In glasses 1 to 6, the total content of Al2O3, La2O3, Y2O3 and Gd2O3 (Al2O3+La2O3+Y2O3+Gd2O3) is preferably 0.1% or more from the viewpoint of improving weather resistance, and more preferably 0.15% or more, 0.20% or more, 0.25% or more, 0.30% or more, 0.35% or more, 0.40% or more, 0.45% or more, and 0.50% or more in that order. On the other hand, from the viewpoint of ensuring the thermal stability of the glass and / or lowering the melting temperature, the total content (Al2O3+La2O3+Y2O3+Gd2O3) is preferably 8.0% or less, and more preferably 7.0% or less, 6.5% or less, 6.0% or less, 5.5% or less, 5.0% or less, 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, and 1.0% or less, in that order.

[0099] When the glass composition as a whole is considered, the cations with a formal valence of +2 tend not to have a prominent effect in terms of improving the transmittance in the visible range or in terms of weather resistance. Therefore, the molar ratio ((MgO+CaO+SrO+BaO) / Li2O) of the total content of the oxides of the cations with a formal valence of +2, MgO, CaO, SrO and BaO, to the content of the oxide of Li ion, Li2O, which is an essential cation, is preferably 2.0 or less, more preferably 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. As described later, the above components are optional components that can be used together with some alkali components to adjust the half value.

[0100] In addition, with regard to the total content of MgO, CaO, SrO, BaO and ZnO, which are oxides of cations having a formal valence of +2, from the viewpoint of improving the transmittance in the visible range, the molar ratio ((MgO+CaO+SrO+BaO+ZnO) / Li2O) to the content of the oxide Li2O of Li ions, which is an essential cation, is preferably 2.0 or less, more preferably 1.5 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. On the other hand, from the viewpoint of improving weather resistance, (MgO+CaO+SrO+BaO+ZnO) / Li2O) is preferably 2.0 or more, more preferably 2.5 or more, 3.0 or more, 3.5 or more, and 4.0 or more in that order. As described later, the above components are optional components that can be used together with some alkaline components when adjusting the half value.

[0101] The BaO content is 0%. It can be 0% or more or more than 0%. BaO is a component that can increase weather resistance by introducing a certain amount, and furthermore, the change in T600 due to the introduction is small. T600 will be described later. BaO can be added for the purpose of increasing the thermal stability of glass and adjusting the melting property. BaO can also be used to adjust the concentration of CuO. The BaO content is preferably 0.5% or more, and more preferably 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more in that order. However, excessive introduction tends to decrease T400. T400 will be described later. From the above viewpoints, the BaO content is preferably 36.0% or less, and is more preferably 35.0% or less, 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less in that order.

[0102] The SrO content is 0%. It can be 0% or more or more than 0%. Like BaO, SrO is a component that is relatively unlikely to reduce weather resistance, and can be added appropriately for reasons such as adjusting the thermal stability of the glass. SrO can also be used to adjust the concentration of CuO. The SrO content is preferably 0.5% or more, and more preferably in the order of 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more. However, since excessive incorporation tends to decrease T400, the SrO content is preferably 30.0% or less, and more preferably in this order: 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less.

[0103] The CaO content is 0%. It can be 0% or more or more than 0%. CaO is a component that is relatively unlikely to reduce weather resistance, and can be added appropriately for reasons such as adjusting the thermal stability of glass. CaO can also be used to adjust the concentration of CuO. The CaO content is preferably 0.5% or more, more preferably 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, 7.0% or more. However, since excessive incorporation tends to decrease T400, the CaO content is preferably 30.0% or less, and more preferably in this order: 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less.

[0104] Among the cations included in the group of major cations described above, Na ions, K ions, and Zn ions tend to deteriorate the weather resistance of glass, so it is difficult to freely use them instead of Li ions, which are essential cations. In addition to this, from the viewpoint of improving the transmittance in the visible or near infrared range, in glasses 1 to 6, the ratio of the total of the Na2O content, the K2O content, and the ZnO content to the Li2O content ((Na2O+K2O+ZnO) / Li2O) is 2.4 or less, and more preferably 2.3 or less, and more preferably 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less, and 0.05 or less, and can also be 0.00. On the other hand, from the viewpoint of reducing the raw material costs of the glass, the molar ratio ((Na2O+K2O+ZnO) / Li2O) can be 0, 0 or more, or more than 0. From the viewpoint of promoting a decrease in Tg and Tm, which will be described later, by mixing a plurality of components, the molar ratio is preferably 0.05 or more, and can also be 0.1 or more, 0.2 or more, or 0.3 or more.

[0105] In addition, the higher the content of Na ions, K ions, and Zn ions, the more difficult it becomes to introduce a large amount of P2O5 in order to maintain weather resistance, and as a result, it becomes difficult to introduce a desired amount of P2O5. From this viewpoint and from the viewpoint of suppressing the deterioration of weather resistance as described above, the total content of Na2O, K2O, and ZnO (Na2O+K2O+ZnO) is preferably 30.0% or less, and more preferably 25.0% or less, 20.0% or less, 15.0% or less, 12.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, and 1.0% or less in that order. The above total content can also be 0%. On the other hand, from the viewpoint of suppressing the raw material cost of glass, the total content (Na2O+K2O+ZnO) can also be 1.0% or more, 2.0% or more, 3.0% or more, or 5.0% or more.

[0106] The Na2O content can be 0%, 0% or more, or more than 0%. Excessive incorporation of Na2O tends to reduce weather resistance. For this reason, the Na2O content is preferably 20.0% or less, more preferably 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, and 8.0% or less in that order. On the other hand, Na2O is an easily available and inexpensive raw material, and can be added appropriately to improve meltability, so the Na2O content can be, for example, 0.5% or more, and can also be 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, or 5.0% or more.

[0107] The K2O content can be 0%, 0% or more, or more than 0%. Excessive incorporation of K2O also tends to reduce weather resistance. Furthermore, it tends to shorten the wavelength of absorption of CuO, so it is desirable not to actively introduce it. From these viewpoints, the K2O content is preferably 20.0% or less, and more preferably 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, and 8.0% or less in that order. On the other hand, K2O can be added appropriately to improve the melting property of glass. From this viewpoint, the K2O content is preferably 0.2% or more, and more preferably 0.5% or more, 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, and 5.0% or more in that order.

[0108] The Cs2O content can be 0%, 0% or more, or more than 0%. Cs2O also tends to reduce weather resistance, so it is desirable not to actively incorporate it. The Cs2O content is preferably 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, and 6.0% or less in that order. On the other hand, in order to adjust thermal stability and meltability, the Cs2O content can be 0.5% or more, 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, and 4.0% or more.

[0109] From the viewpoint of enhancing the meltability of glass, the total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) is preferably 1.8% or more, and more preferably in the following order: 2.1% or more, 2.3% or more, 2.5% or more, 3.5% or more, 4.5% or more, 5.5% or more, 6.5% or more, 7.5% or more, 8.5% or more, 9.5% or more, 10.0% or more, and 10.5% or more. On the other hand, from the viewpoint of further suppressing a decrease in weather resistance, the total content (Li2O+Na2O+K2O) is preferably 35.0% or less, and more preferably in the following order: 33.5% or less, 32.5% or less, 31.5% or less, 30.5% or less, 29.5% or less, 28.5% or less, 27.5% or less, 26.5% or less, 25.5% or less, 24.5% or less, 23.5% or less, 21.5% or less, 20.5% or less, 19.5% or less, 18.5% or less, 17.5% or less, 16.6% or less, 15.5% or less, 14.5% or less, and 13.5% or less. It is preferable that the total content (Li2O+Na2O+K2O) be equal to or less than the above value from the viewpoint of avoiding chipping or cracking of the glass due to stress applied to the glass when the volumetric change of the glass is regulated by other components due to an increase in the thermal expansion coefficient, which increases the amount of expansion and contraction of the glass.

[0110] From the viewpoint of suppressing the deliquescence of the glass, the total content of Na2O and K2O (Na2O+K2O) is preferably 30.0% or less, and more preferably in the following order: 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, and 0.5% or less. By setting the total content of Na2O and K2O (Na2O+K2O) to 0%, it is possible to obtain glass with even less deliquescence. On the other hand, from the viewpoint of suppressing the meltability of the glass and suppressing the decrease in T600 while reducing the raw material costs of the glass, the total content (Na2O+K2O) can be set to 1.0% or more, and can also be set to 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, 8.0% or more, 9.0% or more, 10.0% or more, 11.0% or more, 12.0% or more, 13.0% or more, 14.0% or more, or 15.0% or more.

[0111] When adjusting the thickness of the glass, CuO can be replaced with other components, but in that case, by making the total content of Na2O, K2O, CaO, SrO and BaO (Na2O+K2O+CaO+SrO+BaO) 0% or more, the CuO concentration can be adjusted without significantly changing the position of near-infrared absorption. The total content (Na2O+K2O+CaO+SrO+BaO) is preferably 0.5% or more, and more preferably 1.0% or more, 1.5% or more, 2.0% or more, 2.5% or more, 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, 5.5% or more, 6.0% or more, 6.5% or more, and 7.0% or more in that order. However, since excessive incorporation tends to decrease T400, the total content (Na2O+K2O+CaO+SrO+BaO) is preferably 36.0% or less, and more preferably in the following order: 35.0% or less, 34.0% or less, 33.0% or less, 32.0% or less, 31.0% or less, 30.0% or less, 29.0% or less, 28.0% or less, 27.0% or less, 26.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, 21.0% or less, 20.0% or less, 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, and 9.0% or less. From the standpoint of maximizing the near infrared absorption properties of the glass, the total content (Na2O+K2O+CaO+SrO+BaO) can be 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, or 4.0% or less.

[0112] Regarding weather resistance, one or both of the following can be used as indicators of weather resistance: the suppression of deliquescence of glass, and the suppression of the occurrence of precipitates on the glass surface under high temperature and high humidity. This point will be described further below. In order to further improve weather resistance, it is more preferable to introduce Al2O3, and next it is more preferable to introduce one or more of Y2O3, La2O3, and Gd2O3. Furthermore, BaO can improve the above weather resistance by introducing a relatively large amount, and SrO and CaO need to be introduced in even larger amounts from the viewpoint of improving weather resistance, so the value calculated as "(3 x Al2O3 + Y2O3 + La2O3 + Gd2O3 + BaO / 3 + (CaO + SrO) / 6)" (unit: mol%) is preferably 0% or more, more preferably more than 0%, and is preferably 0.5% or more, 1.0% or more, 2.0% or more, 3.0% or more, 4.0% or more, 5.0% or more, 6.0% or more, 7.0% or more, or 8.0% or more. Furthermore, when the weather resistance and mechanical strength of the glass are important, the following order is more preferable: 9.0% or more, 10.0% or more, 11.0% or more, 12.0% or more, 13.0% or more, 14.0% or more, 15.0% or more, 16.0% or more, 17.0% or more, 18.0% or more, and 19.0% or more. In "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)", "Al2O3" is the Al2O3 content, "Y2O3" is the Y2O3 content, "La2O3" is the La2O3 content, "Gd2O3" is the Gd2O3 content, "BaO" is the BaO content, "CaO" is the CaO content, and "SrO" is the SrO content. In other words, "(3 x Al2O3 + Y2O3 + La2O3 + Gd2O3 + BaO / 3 + (CaO + SrO) / 6)" is the sum of the value calculated by multiplying the Al2O3 content by 3, the value calculated as 1 / 3 of the Y2O3 content, the La2O3 content, the Gd2O3 content, and the BaO content, and the value calculated as 1 / 6 of the sum of the CaO content and the SrO content, and the value thus calculated is expressed in units of % (mol%). On the other hand, if the value of "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is made too large, the meltability of the glass tends to deteriorate and the position of near-infrared absorption tends to shift to the visible light side, and therefore, the value calculated as "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is preferably 40.0% or less, and more preferably 37.0% or less, 35.0% or less, 33.0% or less, 32.0% or less, 30.0% or less, 28.0% or less, 26.0% or less, 25.0% or less, 24.0% or less, 23.0% or less, 22.0% or less, and 21.0% or less in that order.

[0113] The ratio of the value calculated by "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" to the total content of P2O5, Li2O and CuO, i.e., "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6) / (P2O5+Li2O+CuO)" can be 0.0 or more. It is desirable to introduce a certain amount or more of the component selected from the group consisting of Al2O3, Y2O3, La2O3, Gd2O3, BaO, CaO and SrO relative to the essential components P2O5, Li2O and CuO. Therefore, the ratio is preferably 0.01 or more, and more preferably 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, or 0.09 or more in that order. In order to further improve weather resistance, the ratio is more preferably 0.10 or more, and even more preferably 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, or 0.25 or more in that order. On the other hand, if the above ratio is too large, the transmittance characteristics of the glass deteriorate and further the stability of the glass tends to deteriorate. Therefore, the above ratio is preferably 0.36 or less, and more preferably 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, and 0.28 or less, in that order.

[0114] The ZnO content can be 0%, 0% or more, or more than 0%. ZnO is a component that can be added appropriately for reasons such as adjusting the thermal stability of the glass, but it tends to reduce the weather resistance of the glass. In addition, from the viewpoint of ensuring a sufficient amount of P2O5, which is an essential component, the upper limit of the content is preferably 20.0% or less, and more preferably 19.0% or less, 18.0% or less, 17.0% or less, 16.0% or less, 15.0% or less, 14.0% or less, 13.0% or less, 12.0% or less, 11.0% or less, 10.0% or less, 9.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, and 5.0% or less in that order. When the introduction effect of other components is prioritized, the ZnO content can also be 4.0% or less, 3.0% or less, 2.0% or less, or 1.0% or less. On the other hand, when ZnO is introduced to adjust the thermal stability of the glass or to lower Tg and / or Tm, the amount is more preferably 0.4% or more, 0.6% or more, 0.8% or more, 1.0% or more, 1.2% or more, 1.4% or more, 1.6% or more, 1.8% or more, and 2.0% or more, in that order.

[0115] The glass is preferably composed essentially of the above components, but may contain other components as long as the effects of the above components are not hindered. In addition, the glass may contain unavoidable impurities.

[0116] For example, Nb2O5 and ZrO2 may be appropriately incorporated in amounts of more than 0%, 0.1% or more, or 0.2% or more, respectively, as components other than the above components, in order to adjust the weather resistance or mechanical strength of the glass or to improve thermal stability, but the respective contents are preferably 5.0% or less, and more preferably 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, and 0.3% or less in that order. The respective contents of these components may be 0%.

[0117] TiO2, WO3, and Bi2O3 can also be appropriately incorporated in amounts of more than 0%, 0.1% or more, or 0.2% or more, respectively, as components other than the above components, to adjust the weather resistance or mechanical strength of the glass or to improve the thermal stability, without affecting the transmittance of the glass, but each content is preferably 4.0% or less, and more preferably 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, and 0.3% or less in that order. The contents of each of these components can also be 0%.

[0118] Pb, As, Cd, Tl, Be, and Se are all toxic, and therefore it is preferable that the above glass does not contain these as glass components.

[0119] U, Th, and Ra are all radioactive elements, and therefore it is preferable that the above glass does not contain these elements as glass components.

[0120] V, Cr, Mn, Fe, Co, Ni, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, and Tm can increase the coloring of the glass and become a source of fluorescence. Therefore, in the above glass, the total content of these elements on an oxide glass basis is preferably 10 mass ppm or less, and it is more preferable that these elements are not contained as glass components.

[0121] Among them, it is preferable not to use V2O5 because of its toxicity. That is, in one embodiment, glasses 1 to 6 are preferably glasses that do not contain V ions, and in the glass composition based on oxides (molar basis), the V2O5 content is preferably 1.0% or less, more preferably 0.3% or less, 0.1% or less, and 0.01% or less, in that order, and further preferably does not contain V2O5.

[0122] As an example, the ratio of V2O5 to the essential component Li2O, that is, the ratio of the V2O5 content to the Li2O content (V2O5 / Li2O) is preferably 0.0080 or less, and more preferably 0.0048 or less, 0.0028 or less, 0.0018 or less, and 0.0014 or less, in that order.

[0123] It is preferable not to use CoO because it reduces the transmittance of the glass in the visible range and is also toxic. That is, in one embodiment, Glasses 1 to 6 are preferably glasses that do not contain Co ions, and preferably do not contain CoO in the glass composition based on oxides.

[0124] The raw materials for incorporating Ge and Ta into glass are expensive, and therefore it is preferable that the above glass does not contain these elements as glass components.

[0125] Sb (Sb2O3), Sn (SnO2), Ce (CeO2), and SO3 are optional elements that function as fining agents. Among these, Sb (Sb2O3) is a fining agent with a large fining effect. Sn (SnO2) and Ce (CeO2) have a smaller fining effect than Sb (Sb2O3). Adding a large amount of these fining agents tends to intensify the coloring of the glass. Therefore, when adding a fining agent, it is preferable to add Sb (Sb2O3) while taking into consideration the effect of coloring due to the addition.

[0126] The contents of the components capable of functioning as fining agents described below are values ​​in the glass composition based on oxides.

[0127] The Sb2O3 content is expressed as an exclusive percentage. That is, when the total content of all glass components other than Sb2O3, SnO2, CeO2 and SO3 as oxides is 100.0 mass%, the Sb2O3 content is preferably less than 2.0 mass%, and more preferably 1.5 mass% or less, 1.2 mass% or less, 1.0 mass% or less, 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, 0.2 mass% or less, and less than 0.1 mass% in that order. The Sb2O3 content may be 0 mass%. However, from the viewpoint of promoting the oxidation of the glass and increasing the transmittance in the visible range, the Sb2O3 content can be set to 0.01 mass% or more, or can be set to 0.02 mass% or more, 0.03 mass% or more, 0.04 mass% or more, 0.05 mass% or more, 0.06 mass% or more, or 0.08 mass% or more.

[0128] The SnO2 content is also expressed as an external percentage. That is, when the total content of all glass components other than SnO2, Sb2O3, CeO2 and SO3 as oxides is 100.0 mass%, the SnO2 content is preferably less than 2.0 mass%, and more preferably less than 1.0 mass%, more preferably 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, 0.2 mass% or less, and 0.1 mass% in that order. The SnO2 content may be 0 mass%. By setting the SnO2 content within the above range, the clarity of the glass can be improved.

[0129] The CeO2 content is also expressed as an external percentage. That is, when the total content of all glass components other than CeO2, Sb2O3, SnO2 and SO3 as oxides is 100.0 mass%, the CeO2 content is preferably less than 2.0 mass%, less than 1.0 mass%, more preferably 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, 0.2 mass% or less, and less than 0.1 mass% in that order. The CeO2 content may be 0 mass%. The clarity of the glass can be improved by setting the CeO2 content within the above range.

[0130] The SO3 content is also expressed as a percentage. 3、 When the total content of all glass components other than Sb2O3, SnO2, and CeO2 as oxides is taken as 100.0 mass%, the SO3 content is preferably less than 2.0 mass%, more preferably less than 1.0 mass%, even more preferably less than 0.5 mass%, and even more preferably less than 0.1 mass%. The SO3 content may be 0 mass%. By setting the SO3 content in the above range, the clarity of the glass can be improved.

[0131] <Glass properties> (Transmittance characteristics) The above glass is suitable as a glass for a near-infrared cut filter. In the present invention and this specification, unless otherwise specified, the term "transmittance" refers to the external transmittance including reflection loss. The near-infrared blocking ability is the half-value λ, which is the wavelength at which the transmittance is 50% at wavelengths of 550 nm or more. T 50 can be used as an index, the transmittance T1200 at a wavelength of 1200 nm can also be used as an index, the average value of the transmittance in the wavelength range from 1100 nm to 800 nm (referred to as "Ave. T1100-800") can also be used as an index, or the transmittance T750 at a wavelength of 750 nm can also be used as an index. The above glass can also exhibit high transmittance in the visible range. Regarding the transmittance in the visible range, the transmittance T400 at a wavelength of 400 nm can be used as an index, and the transmittance T600 at a wavelength of 600 nm can also be used as an index.

[0132] The transmittance characteristic of glass is a value determined by the following method. The glass sample is processed to have parallel and optically polished flat surfaces, and the external transmittance is measured at wavelengths of 200 to 1200 nm. The external transmittance includes the reflection loss of light rays on the sample surface. The intensity of the light beam perpendicularly incident on one of the optically polished flat surfaces is defined as intensity A, and the intensity of the light beam emerging from the other flat surface is defined as intensity B, and the spectral transmittance B / A, including reflection loss, is calculated. The wavelength at which the spectral transmittance is 50% at wavelengths of 550 nm or more is defined as the half-value λ. T The spectral transmittance at a wavelength of 400 nm is T400, the spectral transmittance at a wavelength of 600 nm is T600, and the spectral transmittance at a wavelength of 1200 nm is T1200. The average value of the spectral transmittance in the wavelength range from 1100 nm to 800 nm is Ave. T1100-800, and the spectral transmittance at a wavelength of 750 nm is T750. Furthermore, if the glass to be measured does not have a thickness that can be converted, the thickness of the glass is taken as d, and the transmittance at each wavelength λ is converted by the following formula A. Various conversion values ​​can then be found from the transmittance characteristics obtained by conversion.

[0133] Equation A: T(λ)=(1-R(λ)) 2 ×exp(log e ((T0(λ) / 100) / (1-R(λ)) 2 )×d / d0)×100

[0134] In formula A, T(λ): converted transmittance at wavelength λ (%), T0(λ): measured transmittance at wavelength λ (%), d: converted thickness (mm), d0: glass thickness (mm), R(λ)=((n(λ)-1) / (n(λ)+1)) 2 where n(λ) is the reflectance at wavelength λ, and n(λ) is the refractive index at wavelength λ. Here, calculations are performed assuming constants of n(λ) = 1.51680 and R(λ) = 0.042165.

[0135] A high T600 value, which is the transmittance in the red region, and a low T1200 value, which is the transmittance in the near-infrared region, can mean that both improved transmittance in the visible region and improved near-infrared blocking ability are achieved. A high T400 value, which is the transmittance in the purple region, can also mean that the transmittance in the visible region is improved. In view of the above, the preferred ranges for T400, T600 and T1200 are as follows: T400 is preferably 70% or more, and more preferably 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, and 80% or more in that order. T400 can be, for example, 98% or less, 97% or less, or 96% or less, but a higher T400 means better visible light transmittance, so it is also preferable for it to exceed the values ​​exemplified above. T600 is preferably 50% or more, and more preferably 55% or more, 56%, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, and 75% or more in that order. T600 can be, for example, 90% or less, 85% or less, or 80% or less, but a higher T600 means better visible light transmittance, so it is also preferable that it exceeds the above-mentioned values. T1200 is preferably 30% or less, more preferably 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less. For the purpose of compatibility with visible light transmittance, T1200 can be, for example, 1% or more, 3% or more, 5% or more, or 7% or more, but since a lower T1200 means a better near-infrared blocking ability, it is also preferable to have a value lower than the above-mentioned values.

[0136] In one embodiment, T1200 can be β1% or less.

[0137] β1 is calculated by the following formula B1: In formula B1, R is the O / P ratio. (Formula B1) β1=64×R-170

[0138] In one embodiment, T1200 can be equal to or less than the values ​​shown by β2, β3, β4, β5, and β6 in the following formulas B2 to B6 (unit: %), where R is the O / P ratio. Formula B2:β2=64×R-175 Formula B3: β3 = 64 × R - 180 Formula B4:β4=80×R-220 Formula B5:β5=80×R-224 Formula B6:β6=80×R-228

[0139] Half-value λ is the wavelength at which the spectral transmittance is 50% at wavelengths of 550 nm or more. T 50 is preferably 600 nm or more, more preferably 610 nm or more, 613 nm or more, 615 nm or more, 617 nm or more, 620 nm or more, 623 nm or more, 625 nm or more, and 628 nm or more in that order. T 50 is preferably 650 nm or less, more preferably 647 nm or less, 645 nm or less, 643 nm or less, 641 nm or less, 640 nm or less, 639 nm or less, and 638 nm or less in that order. T It is preferable that the glass thickness be equal to or less than a certain value in order to achieve both a thinner glass and an improved near-infrared blocking capability. The glass thickness is preferably equal to or less than 0.25 mm.

[0140] Furthermore, since the above glass has excellent absorption characteristics in the near-infrared region, it is possible to suppress "Ave. T1100-800" to 15% or less. "Ave. T1100-800" is preferably 14% or less, and more preferably 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.3% or less, 1.0% or less, 0.3% or less, 0.1% or less, 0.03% or less, and 0.01% or less in that order.

[0141] In addition, since the above glass has excellent absorption characteristics in the near infrared region, T750 can be suppressed to 25% or less. T750 is preferably 24% or less, and more preferably in the order of 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1.3% or less, 1.0% or less, 0.3% or less, 0.1% or less, 0.03% or less, and 0.01% or less.

[0142] As will be described in detail later, in one embodiment, the above glass can be used as a glass for a near-infrared cut filter having a thickness of 0.25 mm or less.

[0143] With regard to the above glass, the following (a) to (h) can be mentioned as preferable transmittance characteristics for a thinned glass for near-infrared cut filters having a thickness of 0.25 mm or less. The above glass preferably satisfies one or more of the following (a) to (h), and may also satisfy two or more. Glass having preferable transmittance characteristics can be obtained by adjusting the glass composition as explained above.

[0144] (a) Wavelength λ at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more T The thickness of the glass at which 50 becomes 633 nm is 0.25 mm or less, At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.

[0145] Regarding (a) above, the wavelength λ at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more TThe thickness of the glass for which 50 is 633 nm is 0.25 mm or less, and it is more preferable that the thickness of the near-infrared cut filter is in the thickness range described below. This also applies to the following (b), (e), and (f).

[0146] (b) The thickness of the glass at which the external transmittance including reflection loss at wavelengths of 550 nm or more is 50% at a wavelength of 633 nm is 0.25 mm or less; In the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less, where β is a value calculated by the following formula B1. In formula B1, R is the O / P ratio of the above glass.

[0147] (Formula B1) β1=64×R-170

[0148] As described above, T1200 can also be the above β2% or less, β3% or less, β4% or less, β5% or less, or β6% or less.

[0149] (c) The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.11 mm T The external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 30% or less, and the external transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

[0150] (d) The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.21 mm T The optical transmittance T1200 including reflection losses at a wavelength of 1200 nm is 25% or less, and the optical transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

[0151] (e) The thickness of the glass at which the external transmittance including reflection loss at wavelengths of 550 nm or more is 50% at a wavelength of 645 nm is 0.25 mm or less; At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.

[0152] (f) Wavelength λ at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more T The thickness of the glass at which 50 becomes 645 nm is 0.25 mm or less, At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less, where β1 is a value calculated by the above-mentioned formula 4.

[0153] (g) The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.23 mm T 50 is in the range of 600 nm to 650 nm, the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 18% or less, and the external transmittance T400 including reflection loss at a wavelength of 400 nm is 70% or more.

[0154] (h) The wavelength λ at which the external transmittance including reflection loss becomes 50% as the transmittance characteristic converted to a thickness of 0.25 mm T The optical transmittance T1200 including reflection losses at a wavelength of 1200 nm is 16% or less, and the optical transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

[0155] (weather resistance) The glass has the composition described above and can exhibit excellent weather resistance. The weather resistance can be, for example, evaluated visually by the method described in the Examples below, and the evaluation result is preferably any one of S to D, more preferably any one of S to C, even more preferably any one of S to B, even more preferably S or A, and even more preferably S. Furthermore, the haze value measured by a haze meter can also be used as an index of weather resistance. Glass having a haze value of 15% or less can be given as an example of glass having even better weather resistance. With regard to weather resistance, it is even more preferable that the result of the visual evaluation is S or A (preferably S) and the haze value measured by a haze meter is 15% or less.

[0156] (Glass transition temperature Tg, temperature at which the endothermic reaction due to melting converges Tm) The glass transition temperature of the above glass is not particularly limited, but from the viewpoint of increasing the transmittance of the glass in the short wavelength region by improving the meltability of the glass and from the viewpoint of reducing the burden on the annealing furnace and the molding device, Tg is preferably 450° C. or less, and more preferably 440° C. or less, 430° C. or less, 420° C. or less, 410° C. or less, and 400° C. or less in that order. From the viewpoint of increasing the chemical durability and / or heat resistance of the glass, Tg is preferably 250° C. or more, and more preferably 260° C. or more, 270° C. or more, 280° C. or more, 290° C. or more, and 300° C. or more in that order.

[0157] The Tg value of the glass can be controlled by adjusting the content of Li2O, Na2O, K2O or their total content, the content of ZnO, the content of MgO, the content of Al2O3 or their total content, or the like.

[0158] The temperature Tm at which the endothermic reaction due to the melting of the glass converges is not particularly limited, but the lower the Tm, the better the melting property, and the more likely it is that devitrification will not occur in the glass even if molding is performed at a higher viscosity. In addition, the better the melting property, the more likely it is that the transmittance of the glass in the visible range of the short wavelength range can be increased. From these viewpoints, Tm is preferably 890°C or less, and more preferably 880°C or less, 870°C or less, 860°C or less, 850°C or less, 840°C or less, 830°C or less, 820°C or less, 810°C or less, 800°C or less, 790°C or less, 780°C or less, 770°C or less, 760°C or less, 750°C or less, 740°C or less, 730°C or less, 720°C or less, 710°C or less, 700°C or less, 690°C or less, 680°C or less, 670°C or less, 660°C or less, and 650°C or less in that order. Although there is no particular limitation on the lower limit of Tm, if Tm is too low, the weather resistance of the glass tends to decrease, so Tm can also be 500°C or more, 550°C or more, 580°C or more, 600°C or more, 620°C or more, or 640°C or more.

[0159] The Tm value of the glass can be controlled by adjusting the content of Li2O, Na2O, K2O or their total content, the content of ZnO, the content of MgO, the content of Al2O3 or their total content, or the like.

[0160] (specific gravity) A lightweight near-infrared cut filter is preferable because it leads to a reduction in the weight of an element or device that the filter is built in. From this point of view, the specific gravity of the glass is preferably 3.40 or less, and more preferably 3.35 or less, 3.30 or less, 3.25 or less, 3.20 or less, 3.15 or less, 3.10 or less, 3.05 or less, 3.00 or less, 2.95 or less, 2.90 or less, 2.85 or less, 2.80 or less, 2.75 or less, 2.70 or less, 2.65 or less, and 2.60 or less, in that order. The specific gravity can be, for example, 2.0 or more, or 2.4 or more, but from the above viewpoint, a low specific gravity is preferable, and therefore it is also preferable for the specific gravity to be below the values ​​exemplified here.

[0161] (Molar Volume) The molar volume M / D of the glass is not particularly limited, but from the viewpoint of increasing the near-infrared absorbing ability by increasing the amount of CuO per unit volume, it is preferable that the molar volume of the glass is smaller. The molar volume can be reduced by substituting P2O5, La2O3, Y2O3, Gd2O3, BaO, K2O, etc. with Li2O, and can be somewhat reduced by substituting Al2O3, CuO, Na2O with Li2O. On the other hand, the molar volume does not change significantly when CaO, ZnO, and SrO are substituted with Li2O, and the molar volume tends to increase when MgO is substituted with Li2O. The molar volume of the glass can be adjusted by adjusting the glass composition in consideration of these trends. The molar volume is preferably 45 cc / mol or less, and more preferably in this order: 43 cc / mol or less, 42 cc / mol or less, 41 cc / mol or less, 40 cc / mol or less, 39.5 cc / mol or less, 39.0 cc / mol or less, 38.5 cc / mol or less, 38.0 cc / mol or less, and 37.5 cc / mol or less. On the other hand, from the viewpoint of maintaining the weather resistance of the glass, the molar volume can be increased, and from this viewpoint, the molar volume of the glass can be 34.0 cc / mol or more, 35.0 cc / mol or more, 36.0 cc / mol or more, 36.5 cc / mol or more, 37.0 cc / mol or more, 37.5 cc / mol or more, 38.0 mol or more, 38.5 cc / mol or more, 39.0 cc / mol or more, or can be 39.5 cc / mol or more.

[0162] <Glass manufacturing method> The above glass can be obtained by mixing, melting, and molding various glass raw materials. For the production method, the description below can also be referred to.

[0163] The near-infrared absorbing glass is suitable as a glass for a near-infrared cut filter. The near-infrared absorbing glass can also be applied to optical elements (lenses, etc.) other than near-infrared cut filters, and can also be applied to various other glass products, and various modifications are possible.

[0164] [Near infrared cut filter] One aspect of the present invention relates to a near-infrared cut filter (hereinafter also simply referred to as "filter") made of the above-mentioned near-infrared absorbing glass.

[0165] The glass constituting the above filter is as described above.

[0166] A specific example of a method for manufacturing the above filter will be described below, however, the following manufacturing method is merely an example and does not limit the present invention.

[0167] The glass melt is prepared by weighing and mixing glass raw materials such as phosphates, oxides, carbonates, nitrates, sulfates, and fluorides to obtain a desired composition, and then melting the raw materials in a melting vessel such as a platinum crucible at, for example, 800°C to 1100°C. At this time, a platinum cover or the like can be used to suppress the volatilization of volatile components. The melting can be carried out in the air, and in order to suppress the change in the valence of Cu, an oxygen atmosphere can be used or oxygen can be bubbled into the molten glass. The molten glass becomes a homogenized glass melt with reduced bubbles (preferably no bubbles) due to stirring and fining. The glass can also be obtained by fining the glass at 900°C to 1100°C, and then lowering the temperature of the glass to 800°C to 1000°C to promote the oxidation of the glass. However, it is not desirable for the melting temperature or fining temperature to be below the liquidus temperature of the glass for a long period of time.

[0168] After stirring and clarifying the molten glass, the glass is poured out, slowly cooled, and then molded into a desired shape. When pouring out the glass, it is preferable to lower the temperature to a temperature close to the liquidus temperature to increase the viscosity of the glass, since this makes it difficult for convection to occur in the poured glass and makes it difficult for striae to form. The slow cooling rate can be selected from the range of -50°C / hr to -1°C / hr, and can also be selected from -30°C / hr or -10°C / hr.

[0169] The glass can be formed by known methods such as casting, pipe pouring, rolling, pressing, etc. The formed glass is transferred to an annealing furnace preheated to near the glass transition point, and slowly cooled to room temperature. In this manner, a near-infrared cut filter can be produced.

[0170] An example of the molding method will be described below. A mold is prepared, which is composed of a flat and horizontal bottom surface, a pair of side walls facing each other in parallel across the bottom surface, and a dam plate blocking one of the openings located between the pair of side walls. A homogenized molten glass is poured into the mold from a platinum alloy pipe at a constant flow rate. The poured molten glass spreads in the mold and is shaped into a glass plate restricted to a constant width by the pair of side walls. The shaped glass plate is continuously drawn out from the opening of the mold. By appropriately setting the molding conditions, such as the shape and dimensions of the mold and the flow rate of the molten glass, a large and thick glass block can be molded. The molded glass molded body is transferred to an annealing furnace that has been heated to a temperature near the glass transition temperature in advance, and is slowly cooled to room temperature. The glass molded body from which distortion has been removed by slow cooling is subjected to mechanical processing such as slicing, grinding, and polishing. In this way, a near-infrared cut filter having a shape according to the application, such as a plate shape or a lens shape, can be obtained. Alternatively, a method can be used in which a preform made of the above glass is molded, and the preform is heated, softened, and press molded (particularly a precision press molding method in which the final product is press molded without performing mechanical processing such as grinding and polishing on the optically functional surface). An optical multilayer film can be formed on the surface of the filter as necessary.

[0171] The near-infrared cut filter has both excellent near-infrared cut capability and high transmittance in the visible range, and is capable of satisfactorily correcting the color sensitivity of a semiconductor imaging device.

[0172] Moreover, the near-infrared cut filter can be applied to an imaging device by combining it with a semiconductor image sensor. The semiconductor image sensor is a package in which a semiconductor imaging element such as a CCD or a CMOS is mounted, and the light receiving section is covered with a light-transmitting member. The light-transmitting member can also be the near-infrared cut filter, or the light-transmitting member can be separate from the near-infrared cut filter.

[0173] The imaging device may also include an optical element such as a lens or a prism for forming an image of a subject on the light receiving surface of the semiconductor image sensor.

[0174] Furthermore, the near-infrared cut filter provides good color sensitivity correction, making it possible to provide an imaging device capable of obtaining images of excellent quality.

[0175] In one embodiment, the near-infrared cut filter may be a near-infrared cut filter having a thickness of 0.25 mm or less. In recent years, with the advent of smartphones, the camera thickness of the image sensor has been significantly reduced, and accordingly, it is desired that the near-infrared cut filter exhibits its performance with a thinner thickness. The near-infrared cut filter is also suitable as such a near-infrared cut filter. The thickness of the near-infrared cut filter may be 0.24 mm or less, 0.23 mm or less, 0.22 mm or less, 0.21 mm or less, 0.20 mm or less, 0.19 mm or less, 0.18 mm or less, 0.17 mm or less, 0.16 mm or less, 0.15 mm or less, 0.14 mm or less, 0.13 mm or less, or 0.12 mm or less. The thickness of the near-infrared cut filter may be, for example, 0.21 mm or 0.11 mm. The thickness of the near-infrared cut filter may be, for example, 0.50 mm or more, but is not limited thereto. In the present invention and this specification, "thickness" refers to the thickness of the sample in the region where the transmittance is measured, and can be measured by a thickness gauge, a micrometer, etc. For example, the thickness may be measured at approximately the center of the position where the transmitted light passes, or the thickness may be measured at multiple points within the spot of the transmitted light and the average value may be calculated.

[0176] With regard to the transmittance characteristics of the near-infrared cut filter, reference can be made to the above descriptions regarding Glasses 1 to 6. With regard to the physical properties of the near-infrared cut filter, reference can be made to the above descriptions regarding Glasses 1 to 6. EXAMPLES

[0177] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments.

[0178] [Examples 1 to 66, Comparative Examples X, A to D] As glass raw materials, phosphates, fluorides, carbonates, nitrates, oxides, etc. were weighed and mixed so that 150g to 300g of glass having the composition shown in Table 1 was obtained, and the mixture was put into a platinum crucible or a quartz crucible, melted at 800°C to 1000°C for 80 to 100 minutes, stirred to degas and homogenize, and then poured into a preheated mold and molded into a predetermined shape. The obtained glass molded body was transferred to an annealing furnace heated to the vicinity of the glass transition temperature and slowly cooled to room temperature. Test pieces were cut out from the obtained glass, and both sides were mirror-polished to a thickness of about 0.2 mm, and various evaluations were performed by the following methods.

[0179] [Evaluation method] <Transmittance characteristics> The transmittance of each test piece at wavelengths of 200 to 1200 nm was measured using a spectrophotometer. From the measurement results, the half value (unit: nm), T400, T600, T1200, and Ave. T1100-800 (unit: %) were calculated as half value 645 nm conversion, half value 633 nm conversion, thickness 0.11 mm conversion, thickness 0.21 mm conversion, thickness 0.23 mm conversion, and thickness 0.25 mm conversion.

[0180] <Glass transition temperature Tg, temperature at which the endothermic reaction due to melting converges Tm> The glass transition temperature Tg and the temperature at which the endothermic reaction due to melting converged Tm were measured using a differential scanning calorimeter (DSC8270) manufactured by Rigaku Co., Ltd. at a heating rate of 10°C / min. The measurement temperature range was from room temperature to 1050°C.

[0181] <Specific gravity> Specific gravity was measured by Archimedes' method.

[0182] <Molar volume> From the measured specific gravity values, the molar volumes were calculated by the method described above.

[0183] <Weather resistance evaluation category> Each test piece was kept in a thermohygrostat at a temperature of 85° C. and a relative humidity of 85% for 3.5 hours. After that, each test piece was subjected to visual appearance evaluation under a fluorescent lamp. From the evaluation results, the weather resistance was evaluated according to the following criteria. S: There is very little haze and / or deposits on the surface. A: There is slight haze and / or deposits on the surface. B: Slightly heavy clouding is observed on the surface and / or precipitates are formed. C: Surface wetting indicating deliquescence is observed but is slight and / or a thick precipitate has formed. D: Deliquescence has occurred to the extent that no obvious reduction in plate thickness is observed, and / or precipitates have formed covering the raw glass. E: Deliquescence has occurred to the extent that a clear reduction in plate thickness is observed, and / or precipitation has occurred to the extent that the raw glass is no longer visible.

[0184] [Table 1-1]

[0185] [Table 1-2]

[0186] [Table 1-3]

[0187] [Table 2-1]

[0188] [Table 2-2]

[0189] [Table 2-3]

[0190]

Table 3-1

[0191]

Table 3-2

[0192]

Table 3-3

[0193]

Table 4-1

[0194]

Table 4-2

[0195]

Table 4-3

[0196]

Table 5-1

[0197]

Table 5-2

[0198]

Table 5-3

[0199]

Table 6-1

[0200] [Table 6-2]

[0201] [Table 6-3]

[0202] [Table 7-1]

[0203] [Table 7-2]

[0204] [Table 7-3]

[0205] From the results shown in the table above, it can be seen that the glasses of Examples 1 to 66 have high transmittance in the visible range (purple to red range) even when thinned, have excellent near-infrared blocking ability, and suppress deterioration in weather resistance. Regarding weather resistance, by comparing Examples 1 to 58 with Example 59, it can be seen that the value calculated as "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is 0 for Example 59, and therefore Examples 1 to 58 have a larger value, and thus have better weather resistance. Comparing Example 59 and Example 60, Example 60, in which the value calculated as "(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)" is 0 and the value of "(Na2O+K2O+ZnO) / Li2O" is greater than 1.4, which is larger than Example 59, has a greater degree of deliquescence than Example 59 and is slightly inferior in terms of weather resistance. In Comparative Example X, the value calculated as “(3×Al2O3+Y2O3+La2O3+Gd2O3+BaO / 3+(CaO+SrO) / 6)” is greater than 0, but the value of “(Na2O+K2O+ZnO) / Li2O” is greater than 11, which is large, and the weather resistance is poor. Comparative Examples A, B, and C are glasses consisting of only three components, P2O5, Li2O, and CuO, and have extremely poor weather resistance. In Comparative Example D, the O / P ratio exceeded 3.2, and the desired transmittance characteristics were not obtained.

[0206] Among the examples that were rated S or A in the above-described visual weather resistance evaluation, the haze value was also determined using a haze meter for Examples 25, 33, 56, and 61 to 66. The determined haze values ​​are shown in Table 8.

[0207] [Table 8]

[0208] As shown in Table 8, compared with Example 25 and Example 33, which were rated as grade A in the visual weather resistance evaluation, the haze values ​​of Examples 56 and 61 to 66, which were rated as grade S in the visual weather resistance evaluation, were low, being 15% or less.

[0209] From the above results, it can be confirmed that in order to achieve both improved transmittance in the visible range and improved near-infrared blocking ability while also keeping the haze value at 15% or less, it is preferable that the O / P ratio is in the range of 3.00 to 3.15 and the value calculated as "(3 x Al2O3 + Y2O3 + La2O3 + Gd2O3 + BaO / 3 + (CaO + SrO) / 6)" (unit: mol %) is in the range of 10.0% to 40.0%.

[0210] Finally, the above-mentioned aspects will be summarized.

[0211] According to one embodiment, glasses 1 to 6 described in detail above are provided.

[0212] In one form, in glasses 1 to 6, the Al2O3 content can be less than 2.0 mol %.

[0213] In one embodiment, in glasses 1 to 6, the total content of Al2O3, La2O3, Y2O3, and Gd2O3 (Al2O3+La2O3+Y2O3+Gd2O3) can be 0.1 mol % or more.

[0214] In one embodiment, glasses 1 to 6 can have the following transmittance characteristics:

[0215] Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which 50 becomes 633 nm is 0.25 mm or less, At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.

[0216] Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which 50 becomes 633 nm is 0.25 mm or less, In the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less; β1 is expressed by the following formula B1: (Formula B1) β1=64×R-170 is a value calculated by In the above formula B1, R is the ratio (O ions / P ions).

[0217] The transmittance characteristic converted to a thickness of 0.11 mm is the half-value λ, which is the wavelength at which the external transmittance including reflection loss is 50%. TThe external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 30% or less, and the external transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

[0218] The transmittance characteristic converted to a thickness of 0.21 mm is the half-value λ, which is the wavelength at which the external transmittance including reflection loss is 50%. T The optical transmittance T1200 including reflection losses at a wavelength of 1200 nm is 25% or less, and the optical transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

[0219] Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which 50 becomes 645 nm is 0.25 mm or less, At the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is 30% or less.

[0220] Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which 50 becomes 645 nm is 0.25 mm or less, In the above thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less; The above β1 is expressed by the following formula B1: (Formula B1) β1=64×R-170 is a value calculated by In the above formula B1, R is the ratio (O ions / P ions).

[0221] According to one embodiment, there is provided a near-infrared cut filter made of the near-infrared absorbing glass described above.

[0222] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by adjusting the composition of the above-mentioned glass compositions as described in the specification, a near infrared absorbing glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.

Claims

1. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; B 2 O 3 and SiO 2 The total content of (B 2 O 3 +SiO 2 ) is 3.0% or less, CuO content is α 1 % or more, α 1 is represented by the following formula 1: (Formula 1) a 1 = 70400×exp(-2.855×R) is a value calculated by In the above formula 1, R is the ratio (O ions / P ions); Near infrared absorbing glass.

2. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as an anion; the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; B 2 O 3 and SiO 2 The total content of (B 2 O 3 +SiO 2 ) is 3.0% or less, Formula 2 below: (Formula 2) C-3200×exp(-2.278×R)≧0 Fulfilling In the above formula 2, C is the CuO content per molar volume of the glass (unit: mmol / cc), R is the ratio (O ions / P ions); Near infrared absorbing glass.

3. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; The following formula 3: (Formula 3) A 1 ={O(P)-O(others)}×Cu A calculated by 1 is 2500 or more, In the above formula 3, O(P) represents the amount of oxygen constituting the oxide of P ion in the oxide-based glass composition, O(others) represents the amount of oxygen obtained by excluding O(P) from the amount of oxygen constituting the oxide of the main cation in the oxide-based glass composition, A near infrared absorbing glass in which Cu indicates the molar CuO content in the glass composition based on oxides.

4. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, Y ions, B ions and Si ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; Formula 4 below: (Formula 4) A 2 ={O(P)-O(others)}×C A calculated by 2 is 700 or more, In the above formula 4, C is the CuO content per molar volume of the glass (unit: mmol / cc), O(P) represents the amount of oxygen constituting the oxide of P ion in the oxide-based glass composition, O(others) indicates the amount of oxygen obtained by subtracting the O(P) from the amount of oxygen constituting the oxide of the main cation in the glass composition based on oxides.

5. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; CuO content is α 2 % or more, α 2 is expressed by the following formula 5: (Formula 5) a 2 = 76522×exp(-2.855×R) is a value calculated by In the above formula 5, R is the ratio (O ions / P ions); Near infrared absorbing glass.

6. Contains four or more major cations selected from the group consisting of P ions, Li ions, Cu ions, Al ions, Ba ions, Sr ions, Ca ions, Mg ions, Zn ions, K ions, Na ions, La ions, Gd ions, and Y ions; Contains P ions, Li ions and Cu ions as essential cations; Contains at least O ions as anions, the ratio of the O ion content to the P ion content (O ion / P ion) is 3.15 or less; In the glass composition expressed in anion %, the content of O ions is 90.0 anion % or more, In the oxide-based glass composition, On a molar basis, The total content of the oxides of the main cations is 90.0% or more; MgO and Al 2 O 3 The total content of MgO and Al 2 O 3 ) is 8.0% or less, Li 2 Na relative to O content 2 O content, K 2 The ratio of the total O content and the total ZnO content ((Na 2 O+K 2 O + ZnO) / Li 2 O) is 2.4 or less; Formula 6 below: (Formula 6) C-3478×exp(-2.278×R)≧0 Fulfilling In the above formula 6, C is the CuO content per molar volume of the glass (unit: mmol / cc), R is the ratio (O ions / P ions); Near infrared absorbing glass.

7. Na 2 O content, K 2 The near infrared absorbing glass according to claim 1 , wherein the total O content is less than 15.0 mol %.

8. A 2 O 3 The near infrared absorbing glass according to claim 1 , wherein the content is less than 2.0 mol %.

9. A 2 O 3 , La 2 O 3 , Y 2 O 3 and Gd 2 O 3 The total content (Al 2 O 3 +La 2 O 3 +Y 2 O 3 +Gd 2 O 3 9. The near infrared absorbing glass according to claim 1, wherein the content of Cd is 0.1 mol % or more.

10. Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which the optical fiber diameter becomes 633 nm is 0.25 mm or less, 10. The near infrared absorbing glass according to claim 1, wherein, in the thickness, an external transmittance T600 including reflection losses at a wavelength of 600 nm is 50% or more, and an external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 30% or less.

11. Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which the optical fiber diameter becomes 633 nm is 0.25 mm or less, In the thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less; β1 is represented by the following formula B1: (Formula B1) β1=64×R-170 is a value calculated by In the formula B1, The near infrared absorbing glass according to claim 1 , wherein R is the ratio (O ions / P ions).

12. The transmittance characteristic converted to a thickness of 0.11 mm is the half-value λ, which is the wavelength at which the external transmittance including reflection loss is 50%. T 10. The near infrared absorbing glass according to claim 1, wherein T50 is in the range of 600 nm to 650 nm, an external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 30% or less, and an external transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

13. The transmittance characteristic converted to a thickness of 0.21 mm is the half-value λ, which is the wavelength at which the external transmittance including reflection loss is 50%. T 10. The near infrared absorbing glass according to claim 1, wherein T50 is in the range of 600 nm to 650 nm, an external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 25% or less, and an external transmittance T400 including reflection losses at a wavelength of 400 nm is 70% or more.

14. Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which the optical fiber diameter becomes 645 nm is 0.25 mm or less, 10. The near infrared absorbing glass according to claim 1, wherein, in the thickness, an external transmittance T600 including reflection losses at a wavelength of 600 nm is 50% or more, and an external transmittance T1200 including reflection losses at a wavelength of 1200 nm is 30% or less.

15. Half-value λ is the wavelength at which the external transmittance including reflection loss is 50% at wavelengths of 550 nm or more. T The thickness of the glass at which the optical fiber diameter becomes 645 nm is 0.25 mm or less, In the thickness, the external transmittance T600 including reflection loss at a wavelength of 600 nm is 50% or more, and the external transmittance T1200 including reflection loss at a wavelength of 1200 nm is β1% or less; The β1 is represented by the following formula B1: (Formula B1) β1=64×R-170 is a value calculated by In the formula B1, The near infrared absorbing glass according to claim 1 , wherein R is the ratio (O ions / P ions).

16. A near infrared cut filter comprising the near infrared absorbing glass according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Glass, glass product and preparation method of glass product

    CN110255897A

  • Low melting point glass for edgeecladding disc laser glass

    JP1980003336A

  • Filter glass for absorbing near infrared ray

    JP1982149845A

  • Near-infrared ray cut filter glass

    WO2011046155A1

  • Colored glass

    JP2014012630A